Method for producing resin composition

JP2025010219A5Pending Publication Date: 2025-02-07ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024188360
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-03
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing methods for producing resin compositions with organic fibers, such as cellulose fibers, fail to achieve the desired improvement in mechanical properties like tensile elongation and stiffness due to inadequate dispersion and kneading conditions, which are crucial for applications requiring high compatibility and stability.

Method used

A method involving the use of an extruder with specific kneading zones, including narrow gap zones, pressure drop zones, and high pressure zones, along with controlled gap and pressure ratios, to uniformly disperse organic fibers within the polymer matrix, minimizing damage and enhancing mechanical properties.

Benefits of technology

The method produces resin compositions with molded articles exhibiting high and stable tensile elongation and rigidity, suitable for demanding applications by ensuring uniform dispersion and minimizing fiber damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a method for producing a resin composition capable of forming a molded body having an excellent tensile elongation and / or rigidity, and more preferably a molded body that highly and stably achieves both a tensile elongation and a rigidity.SOLUTION: There is provided a method for producing a resin composition containing a first component and a second component, comprising a kneading step for kneading the first component and the second component by an extruder provided with a kneading zone that includes a plurality of narrow gap zones in which a gap between a cylinder inner wall and a screw is 2 mm or less. There is also provided a method for producing a resin composition that contains a first component and a second component, comprising a kneading step for kneading the first component and the second component by an extruder provided with a kneading zone that includes a plurality of high-pressure zones in which a pressure is 0.1 MPa or higher. A pressure [P1] of the highest pressure zone having the maximum pressure among the plurality of high-pressure zones is 0.5 MPa or higher, and a ratio [P1 / P2] of the pressure [P1] to an average pressure [P2] of the pressures in the high-pressure zones other than the maximum pressure zone is greater than 1 and 100 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a resin composition. [Background technology]

[0002] Thermoplastic resins are light and have excellent processing properties, and therefore are widely used in many fields such as automobile parts, electrical and electronic parts, office equipment housings, and precision parts. However, since the mechanical properties and dimensional stability of the resin alone are often insufficient, composites in which a filler is dispersed in a polymer continuous phase or a polymer dispersed phase is generally used. In recent years, the use of organic fibers such as cellulose fibers as the above-mentioned filler has been considered. Cellulose fibers are promising as a filler for environmentally friendly resin compositions because they are a material that places little burden on the environment, have a low specific gravity, and can have an excellent effect of improving the physical properties of resin compositions. However, it is not always easy to disperse organic fibers such as cellulose fibers well in polymers (resins). For example, when organic fibers and resins are melt-kneaded using an extruder, depending on the kneading conditions, the intended effect of improving the physical properties may not be imparted to the resin composition. The same is true when forming a polymer alloy having a polymer continuous phase and a polymer dispersed phase, and depending on the kneading conditions, the desired effect of improving the physical properties may not be obtained during melt-kneading using an extruder.

[0003] Regarding kneading of a resin composition, for example, Patent Document 1 describes a method for producing a polyamide resin composition using a twin-screw extruder, in which the resin pressures in the kneading zone and the full flight zone satisfy a specific relationship. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-108547 A Summary of the Invention [Problem to be solved by the invention]

[0005] The method described in Patent Document 1 is intended to obtain a molded article having excellent residence stability, heat aging resistance, surface appearance, etc., but does not focus on a method for expressing the physical property improvement effect of a filler and / or a dispersed phase, such as an organic fiber such as cellulose fiber, and / or a polymer dispersed phase, to an intended degree in a resin composition containing the filler and / or the dispersed phase. Resin compositions containing organic fibers such as cellulose fiber and / or a polymer dispersed phase have been considered for application to various applications such as automobile applications due to their advantageous properties according to their material composition (for example, light weight and dimensional stability of cellulose fibers). For example, in applications with strict performance requirements such as automobile applications, it is desired to achieve a high degree of compatibility of multiple properties (especially tensile elongation and rigidity) and to stably express these properties. However, the prior art does not provide a resin composition capable of forming a molded article having such excellent physical properties.

[0006] One aspect of the present invention aims to solve the above-mentioned problems and provide a method for producing a resin composition capable of forming a molded article having excellent tensile elongation and / or rigidity, more preferably a molded article having both tensile elongation and rigidity at a high level and in a stable manner. [Means for solving the problem]

[0007] The present disclosure encompasses the following aspects. [1] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes a kneading step of kneading a first component and a second component using an extruder equipped with a kneading zone including multiple narrow gap zones in which the gap between the inner wall of a cylinder and the screw is 2 mm or less. [2] The method described in aspect 1 above, wherein the ratio [G1 / G2] of the gap [G1] of the narrowest gap zone, which has the smallest gap among the plurality of narrow gap zones, to the average gap [G2] of the narrowest gap zones other than the narrowest gap zone, is 0.001 or more and less than 1. [3] The method according to aspect 1 or 2, wherein the ratio [G1 / G3] of the gap [G1] of the narrowest gap zone, which has the smallest gap among the plurality of narrow gap zones, to the gap [G3] of each of the narrow gap zones other than the narrowest gap zone is 0.001 or more and less than 1. [4] The second component comprises organic fibers; The organic fibers fed to the extruder have an average fiber length of 1 μm to 10,000 μm, The method according to any one of the above-mentioned aspects 1 to 3, wherein a ratio of the gap [G1] of a narrowest gap zone, which has the smallest gap among the plurality of narrow gap zones, to the average fiber length is 0.001 to 10. [5] The second component comprises organic fibers; The organic fibers fed to the extruder form particles having an average particle diameter of 1 μm to 10,000 μm, The method according to any one of the above-mentioned aspects 1 to 4, wherein the ratio of the gap [G1] of the narrowest gap zone, which has the smallest gap among the plurality of narrow gap zones, to the average particle size is 0.001 to 10. [6] The method according to any one of aspects 1 to 5, wherein the improvement rate of the flexural modulus per unit mass of the mixture in each of the plurality of narrow gap zones is greater than the maximum value of the flexural modulus per unit mass of the mixture in each zone other than the narrow gap zone. [7] for each of the narrow gap zones: The pressure of the inflow into the narrow gap zone is 0.5 to 20 MPa; and The method according to any one of the above aspects 1-6, wherein the ratio of the pressure of the effluent from the narrow gap zone to the pressure of the influent to the narrow gap zone is 0.2 or less. [8] The method according to any one of the above aspects 1 to 7, wherein for each of the narrow gap zones, the content of the second component in the inflow to the narrow gap zone is 15 to 90 mass %. [9] The method according to any one of the above aspects 1 to 8, wherein in the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after it has passed through the plurality of narrow gap zones to cool the mixture.

[10] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes a step of mixing a first component and a second component using an extruder having a mixing zone including a pressure drop zone; the pressure drop zone is a region in which the pressure of the inflow into the pressure drop zone is 0.5 to 20 MPa, and the ratio of the pressure of the effluent from the pressure drop zone to the pressure of the inflow into the pressure drop zone is 0.2 or less; The influent to the pressure drop zone has a content of the second component of 15 to 90 mass %. ,method.

[11] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes a step of mixing a first component and a second component using an extruder having a mixing zone including a pressure drop zone; the pressure drop zone is a region in which the pressure of the inflow into the pressure drop zone is 0.5 to 20 MPa, and the ratio of the pressure of the effluent from the pressure drop zone to the pressure of the inflow into the pressure drop zone is 0.2 or less; The method according to claim 1, further comprising the step of adding an additional polymer having a lower temperature than the mixture to the mixture after it has passed through the pressure drop zone in the compounding step to cool the mixture.

[12] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes a kneading step of kneading a first component and a second component by an extruder having a kneading zone including a plurality of high pressure zones having a pressure of 0.1 MPa or more; The method according to claim 1, wherein the pressure [P1] of a highest pressure zone having the highest pressure among the plurality of high pressure zones is 0.5 MPa or more, and the ratio [P1 / P2] of the pressure [P1] to the average pressure [P2] of the high pressure zones other than the highest pressure zone is greater than 1 and less than 100.

[13] The method according to claim 12, wherein the ratio [P1 / P3] of the pressure [P1] to the pressure [P3] in each of the high pressure zones other than the highest pressure zone is greater than 1 and not greater than 100.

[14] The method according to any one of claims 12 to 13, wherein the ratio of zone length to cylinder inner diameter of each of the plurality of high pressure zones is 1 to 30.

[15] The method according to any one of the above aspects 12 to 14, wherein a ratio of the zone length / cylinder inner diameter ratio of the highest pressure zone to the zone length / cylinder inner diameter ratio of each high pressure zone other than the highest pressure zone is 1 or more.

[16] The method according to any one of aspects 12 to 15, wherein the improvement rate of the flexural modulus per unit mass of the mixture in each of the plurality of high pressure zones is greater than the maximum value of the flexural modulus per unit mass of the mixture in each zone other than the high pressure zone.

[17] for each of the high pressure zones: The pressure of the influent to the high pressure zone is 0.5 to 20 MPa; and 17. The method of any one of aspects 12 to 16, wherein the ratio of the pressure of the effluent from the high pressure zone to the pressure of the influent to the high pressure zone is 0.2 or less.

[18] The method according to any one of Aspects 12 to 17, wherein for each of the high pressure zones, the content of the second component in the influent to the high pressure zone is 15 to 90 mass %.

[19] The method according to any one of Aspects 12 to 18, wherein in the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after it has passed through all of the multiple high-pressure zones to cool the mixture.

[20] The method according to any one of Aspects 1 to 19, further comprising, prior to the kneading step, a step of adding the second component to a melt of the first component to obtain a premixture, and supplying the premixture to the kneading zone.

[21] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The dispersive mixing zone includes a first dispersive mixing zone and a second dispersive mixing zone, which are different from each other in one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume rate; an increment [E1] of the tensile elongation of the outflow from the first dispersive mixing zone relative to the tensile elongation of the inflow to the first dispersive mixing zone, and an increment [E2] of the tensile elongation of the outflow from the second dispersive mixing zone relative to the tensile elongation of the inflow to the second dispersive mixing zone satisfy the relationship [E1]>[E2]; A method in which an increment [M1] in the bending modulus of an output from the first dispersive mixing zone relative to the bending modulus of an influent into the first dispersive mixing zone and an increment [M2] in the bending modulus of an output from the second dispersive mixing zone relative to the bending modulus of an influent into the second dispersive mixing zone satisfy the relationship [M1]<[M2].

[22] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The method comprises varying one or more of the following in the cylinder length direction in the dispersion mixing zone: zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, and void volume ratio, thereby varying the ratio [ΔE / ΔM] of the change in tensile elongation ΔE (%) per value (l / d) obtained by dividing the progression length l (mm) of the mixture in the cylinder by the cylinder inner diameter d (mm) to the change in flexural modulus ΔM (GPa) per l / d in the cylinder length direction.

[23] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method further comprising: a dispersive mixing step of dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The dispersive mixing zone and the distributive mixing zone are different from each other in at least one selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume ratio; an increment [EA] of the tensile elongation of the outflow from the dispersive mixing zone relative to the tensile elongation of the inflow to the dispersive mixing zone and an increment [EB] of the tensile elongation of the outflow from the distributive mixing zone relative to the tensile elongation of the inflow to the distributive mixing zone satisfy the relationship [EA]>[EB]; A method in which the increment [MA] of the bending modulus of the output from the dispersive mixing zone relative to the bending modulus of the influent to the dispersive mixing zone and the increment [MB] of the bending modulus of the output from the distributive mixing zone relative to the bending modulus of the influent to the distributive mixing zone satisfy the relationship [MA] > [MB].

[24] A method for producing a resin composition containing a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber, a polymer different from the first component, or a combination thereof; The method further comprising: a dispersive mixing step of dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The method according to claim 1, wherein the concentration of the second component in the dispersive mixing zone [CA] is 10% by mass to 90% by mass, the concentration of the second component in the distributive mixing zone [CB] is 1% by mass to 50% by mass, and the ratio [CA] / [CB] is 2 to 90.

[25] The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The dispersive mixing zone includes a first dispersive mixing zone and a second dispersive mixing zone, which are different from each other in one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume rate; an increment [E1] of the tensile elongation of the outflow from the first dispersive mixing zone relative to the tensile elongation of the inflow to the first dispersive mixing zone, and an increment [E2] of the tensile elongation of the outflow from the second dispersive mixing zone relative to the tensile elongation of the inflow to the second dispersive mixing zone satisfy the relationship [E1]>[E2]; The method according to any one of the above aspects 1 to 20, wherein an increment [M1] in the bending modulus of the output from the first dispersive mixing zone relative to the bending modulus of the inflow into the first dispersive mixing zone and an increment [M2] in the bending modulus of the output from the second dispersive mixing zone relative to the bending modulus of the inflow into the second dispersive mixing zone satisfy the relationship [M1]<[M2].

[26] The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; 21. The method according to any one of aspects 1 to 20, wherein in the dispersion mixing zone, one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, and void volume ratio are varied in the cylinder length direction, thereby changing a ratio [ΔE / ΔM] of a change in tensile elongation ΔE (%) per value (l / d) obtained by dividing the progression length l (mm) of the mixture in the cylinder by the cylinder inner diameter d (mm) to a change in flexural modulus ΔM (GPa) per l / d in the cylinder length direction.

[27] The method, a dispersive mixing step of dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The dispersive mixing zone and the distributive mixing zone are different from each other in at least one selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume ratio; an increment [EA] of the tensile elongation of the outflow from the dispersive mixing zone relative to the tensile elongation of the inflow to the dispersive mixing zone and an increment [EB] of the tensile elongation of the outflow from the distributive mixing zone relative to the tensile elongation of the inflow to the distributive mixing zone satisfy the relationship [EA]>[EB]; A method according to any one of the above aspects 1 to 20, wherein an increment [MA] of the bending modulus of the output from the dispersive mixing zone relative to the bending modulus of the inflow into the dispersive mixing zone and an increment [MB] of the bending modulus of the output from the dispersive mixing zone relative to the bending modulus of the inflow into the dispersive mixing zone satisfy the relationship [MA]>[MB].

[28] The method, a dispersive mixing step of dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, 21. The method according to any one of the above aspects 1 to 20, wherein a concentration [CA] of the second component in the dispersive mixing zone is 10% by mass to 90% by mass, a concentration [CB] of the second component in the distributive mixing zone is 1% by mass to 50% by mass, and a ratio [CA] / [CB] is 2 to 90.

[29] The method according to any one of Aspects 21 to 28, further comprising, prior to the dispersive mixing step, adding the second component to a melt of the first component to obtain a premix, and supplying the premix to the dispersive mixing zone.

[30] The method of any one of aspects 1 to 29, wherein the second component comprises organic fibers.

[31] The method of claim 30, wherein the organic fibers are cellulose fibers.

[32] The method according to any one of the above aspects 30 to 31, wherein the organic fibers in the resin composition have an average fiber diameter of 1,000 nm or less and an average fiber length / average fiber diameter ratio of 30 or more.

[33] The method according to any one of the above aspects 30 to 32, wherein the organic fibers are supplied to the extruder in a dry form. Effect of the Invention

[0008] According to one aspect of the present invention, there is provided a method for producing a resin composition capable of forming a molded article having excellent tensile elongation and / or rigidity, more preferably a molded article having both tensile elongation and rigidity at a high level and in a stable manner. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a diagram illustrating steps of a method for producing a resin composition according to a first embodiment of aspect A of the present invention. [Diagram 2] FIG. 2 is a diagram illustrating steps of a method for producing a resin composition according to a second embodiment of aspect A of the present invention. [Diagram 3] FIG. 4 is a diagram illustrating steps of a method for producing a resin composition according to a third embodiment of aspect A of the present invention. [Figure 4] FIG. 2 is a diagram illustrating steps of a method for producing a resin composition according to a first embodiment of aspect B of the present invention. [Diagram 5] FIG. 2 is a diagram illustrating the change behavior of tensile elongation and flexural modulus in the method according to the first embodiment of aspect B of the present invention. [Figure 6] FIG. 4 is a diagram illustrating steps of a method for producing a resin composition according to a second embodiment of aspect B of the present invention. [Figure 7] FIG. 13 is a diagram illustrating the behavior of changes in tensile elongation and flexural modulus in the method according to the second embodiment of aspect B of the present invention. [Figure 8] FIG. 2 is a diagram illustrating steps in a method for producing a resin composition according to embodiment C of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, exemplary embodiments of the present invention (hereinafter, abbreviated as "present embodiments") will be described, but the present invention is not limited to these embodiments. Note that, unless otherwise specified, the characteristic values ​​of the present disclosure are values ​​measured by the method described in the [Examples] section of the present disclosure or a method that is understood to be equivalent to the above by a person skilled in the art.

[0011] One aspect of the present disclosure provides a method for producing a resin composition comprising a first component and a second component. In one aspect, the first component is a polymer, and the second component is an organic fiber, a polymer, or a combination thereof. In one aspect, the polymer in the second component is different from the first component. In one aspect, the first component constitutes a continuous phase in the resin composition. In one aspect, the organic fiber that may be included in the second component is dispersed in the first component in the resin composition. In one aspect, the polymer that may be included in the second component is present as a dispersed phase in the continuous phase of the first component in the resin composition.

[0012] The method of the present disclosure includes a kneading step in which the first component and the second component are kneaded by an extruder equipped with a kneading zone. When the first component and the second component are kneaded by an extruder to produce a resin composition, in order to uniformly finely disperse the second component in the first component, both the fineness of the second component itself and the improvement of the dispersion state of the second component in the first component are necessary. In order to finely disperse the second component, it is necessary to apply a certain amount of strong force to the mixture, but such a force may cause damage to the second component (for example, breakage of the organic fiber due to bending when the second component contains organic fiber). Therefore, it is desirable that the kneading conditions are designed so that they are necessary for finely dispersing the second component but do not apply an excessive load to the second component. In the method of the present disclosure, the first component and the second component are kneaded in a kneading zone controlled to specific kneading conditions.

[0013] For example, in the method of the below-described aspect A which is an exemplary embodiment of the present disclosure, a partial region within the kneading zone is a zone in which a large force is applied to the mixture. In the method of aspect B described below, which is an exemplary embodiment of the present disclosure, a region for mainly improving the tensile elongation and flexural modulus of the mixture is provided in the dispersing and mixing zone, and a region for mainly improving the flexural modulus. Additionally, in the method of aspect C below, which is an exemplary embodiment of the present disclosure, the first component and the second component are dispersively mixed and distributively mixed in a specific aspect. In this disclosure, dispersive mixing refers to a mixing form accompanied by a substantial change in size of the second component (disintegration, cutting, defibration of aggregates, etc.), and distributive mixing refers to a mixing form accompanied by a change in the dispersion state of the second component in the first component, but without a substantial change in size of the second component. In one embodiment, a substantial change in size is a size change of 30% or more with respect to 100% of the original size in at least one size index. According to the method according to one embodiment of the present disclosure, the unique kneading form as described above makes it possible to uniformly finely disperse the second component in the first component while avoiding damage to the second component.

[0014] In the method of the present disclosure, when the first component and the second component are melt-mixed using an extruder, the second component may be melt-kneaded with the first component in the form of a dry body or a slurry (e.g., a water dispersion). In a preferred embodiment, the second component is supplied to the extruder in the form of a dry body. The heating temperature throughout the melt-kneading is preferably a temperature that is equal to or higher than the glass transition point of the first component, but does not significantly exceed the glass transition point and / or melting point.

[0015] In this disclosure, the glass transition point refers to the peak top temperature at which the storage modulus is significantly reduced and the loss modulus is maximized when measured using a dynamic viscoelasticity measuring device at a heating rate of 2°C / min from 23°C and an applied frequency of 10Hz. When two or more loss modulus peaks appear, it refers to the peak top temperature of the peak on the highest temperature side. In this disclosure, the melting point refers to the peak top temperature of the endothermic peak that appears when the temperature is raised from 23°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), and when two or more endothermic peaks appear, it refers to the peak top temperature of the endothermic peak on the highest temperature side.

[0016] The water content of the polymer to be melt-kneaded is preferably 0.2% by mass or less, or 0.1% by mass or less, or 0.07% by mass or less. From the viewpoint of ease of process control, the water content may be, for example, 0.001% by mass or more.

[0017] For melt kneading, a single screw extruder or a twin screw extruder may be used, and a twin screw extruder is preferred in terms of controlling the dispersibility of the second component. The L / D obtained by dividing the cylinder length (L) of the extruder by the screw diameter (D) is preferably 40 or more, and particularly preferably 50 or more. The screw rotation speed during kneading is preferably in the range of 100 to 800 rpm, and more preferably in the range of 150 to 600 rpm. These vary depending on the screw design.

[0018] Each screw in the cylinder of the extruder is optimized by combining a full-flight screw with an elliptical two-blade screw shape, a kneading element called a kneading disk, and the like. In the optimization, the screw element may have a notch or a flow dividing structure. In addition, a dam structure called a seal ring may be arranged in the screw configuration. In one embodiment, the screw cross section may be configured as a multiple-strand cross section such as zero-strand, one-strand, two-strand, three-strand, or four-strand. In addition, these screw cross sections may be eccentric. Hereinafter, aspects A to C, which are exemplary embodiments of the present disclosure, will be specifically described.

[0019] [Aspect A] In the method according to aspect A, a part of the kneading zone is a zone where a large force is applied to the mixture (also referred to as a high-load zone in the present disclosure) (more specifically, a narrow gap zone, a pressure drop zone, or a high-pressure zone, which will be described later). By providing a high-load zone and other zones in the kneading zone, the high-load zone realizes the fineness of the second component, which can greatly contribute to improving the desired physical properties of the resin composition, while the other zones make the mixing conditions gentle so that the force applied to the second component is minimized, thereby avoiding damage to the second component. According to such a process, the second component can be uniformly finely dispersed in the first component while avoiding damage to the second component, so that in one aspect, a resin composition capable of forming a molded product having excellent tensile elongation and / or flexural modulus, more preferably a molded product having a high degree of tensile elongation and flexural modulus, can be produced. More specifically, Aspect A includes the following first to third embodiments.

[0020] First Embodiment A first embodiment provides a method including a kneading step of kneading a first component and a second component using an extruder equipped with a kneading zone including multiple narrow gap zones having a gap between an inner wall of a cylinder and a screw of 2 mm or less.

[0021] FIG. 1 is a diagram for explaining the steps of the method for producing a resin composition according to the first embodiment. In the first embodiment, an extruder 100 includes a kneading zone 101 and may optionally include a melting zone 102. For example, the method of the first embodiment may further include a step of obtaining a premix by adding a second component a2 to a melt obtained by melting a first component a1 in a melting zone 102 before the kneading step in the kneading zone 101, and the premix may be supplied to the kneading zone 101. In normal kneading using an extruder, a strong shear is applied to the mixture in the first melting zone, so that when the second component is added to the first component in a molten state from an addition port (side feeder) after the first component passes through the melting zone, thermal deterioration of the second component can be suppressed. The mixture is kneaded in the kneading zone 101 and taken out as a resin composition b.

[0022] In one embodiment, the kneading zone 101 includes a plurality of narrow gap zones N1, N2, and N3 in which the gap between the cylinder inner wall and the screw (also referred to as the cylinder gap in this disclosure) is 2 mm or less. In this disclosure, the cylinder gap means the gap of the widest flow path among the flow paths through which the mixture can pass from the upstream to the downstream of the extruder. For example, in a screw element such as a double-start flight screw, the gap in the minor axis direction of the screw radial cross section is the cylinder gap. Also, for example, in a screw element such as a seal ring, the gap between the screw and the cylinder is the cylinder gap. Although FIG. 1 shows an example in which there are three narrow gap zones, the number of narrow gap zones in the kneading zone may be selected according to the purpose, and may be, for example, 2 or more, or 3 or more, and may be, for example, 10 or less, or 5 or less.

[0023] Among the multiple narrow gap zones N1, N2, and N3, the ratio [G1] (hereinafter also simply referred to as [G1]) of the narrowest gap zone in which the cylinder gap is the smallest to the average cylinder gap [G2] of the narrow gap zones other than the narrowest gap zone is, in one embodiment, 0.001 or more, or 0.01 or more, or 0.1 or more, from the viewpoint of favorably advancing the refinement of the second component, and in one embodiment, is less than 1, or 0.5 or less, or 0.3 or less, from the viewpoint of suppressing damage to the second component. Note that the above average value [G2] means the cylinder gap value of the zone if there is one corresponding zone, and means the arithmetic average of the cylinder gap values ​​of the zone if there are two or more corresponding zones.

[0024] The ratio [G1 / G3] of the above [G1] to the cylinder gap [G3] of each of the narrow gap zones other than the narrowest gap zone is, in one embodiment, 0.001 or more, or 0.01 or more, or 0.1 or more, from the viewpoint of smoothly progressing the refinement of the second component, and, in one embodiment, is less than 1, or 0.5 or less, or 0.3 or less, from the viewpoint of suppressing damage to the second component.

[0025] [G1] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.

[0026] [G2] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.

[0027] [G3] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.

[0028] When the second component contains organic fibers, in one embodiment, the organic fibers fed to the extruder have an average fiber length of 1 μm to 10,000 μm. The average fiber length in the present disclosure is a value measured by a scanning electron microscope (SEM) as described later. In one embodiment, the average fiber length is 1 μm or more, or 10 μm or more, or 50 μm or more, and in one embodiment, 10,000 μm or less, or 1,000 μm or less, or 750 μm or less, or 600 μm or less. In one embodiment, the ratio of the above [G1] to the average fiber length is preferably 0.001 or more, or 0.01 or more, or 0.1 or more from the viewpoint of suppressing damage to the organic fibers, and is preferably 10 or less, or 5 or less, or 1 or less from the viewpoint of smoothly advancing the microfabrication of the organic fibers.

[0029] When the second component contains organic fibers, in one embodiment, the organic fibers fed to the extruder form particles having an average particle size of 1 μm to 10,000 μm. In one embodiment, the average particle size of the particles is 1 μm or more, or 10 μm or more, or 50 μm or more, and in one embodiment, 10,000 μm or less, or 1,000 μm or less, or 750 μm or less, or 500 μm or less. In one embodiment, the ratio of [G1] to the average particle size of the particles is preferably 0.001 or more, or 0.01 or more, or 0.1 or more from the viewpoint of suppressing damage to the organic fibers, and is preferably 10 or less, 5 or less, or 1 or less from the viewpoint of favorably advancing the micronization of the organic fibers. The average particle size in the present disclosure is a d50 particle size measured with a powder tester (for example, a powder tester manufactured by Hosokawa Micron Corporation, model number: PT-X).

[0030] The content of the second component in the inflow into each narrow gap zone is preferably 15 mass% or more, or 20 mass% or more, or 30 mass% or more, from the viewpoint of obtaining a good physical property improving effect by the second component by containing the second component at a desired concentration in the resin composition, and is preferably 90 mass% or less, or 80 mass% or less, or 70 mass% or less, from the viewpoint of good progress in the fine particle size reduction of the second component.

[0031] The pressure of the inflow into each narrow gap zone is preferably 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more from the viewpoint of favorably advancing the refinement of the second component, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less from the viewpoint of suppressing damage to the second component. Note that, in one embodiment, the pressure of the inflow into each narrow gap zone is substantially equal to the pressure of the mixture in each narrow gap zone.

[0032] For each narrow gap zone, the ratio of the pressure of the outflow from the narrow gap zone to the pressure of the inflow into the narrow gap zone is preferably 0.2 or less, or 0.15 or less, or 0.1 or less, in terms of being able to increase the pressure of the inflow into the narrow gap zone and to favorably advance the pulverization of the second component, and is preferably 0.0001 or more, or 0.001 or more, or 0.01 or more, in terms of suppressing damage to the second component due to a sudden pressure change of the mixture. In one embodiment, the pressure of the outflow from each narrow gap zone is substantially equal to the pressure of the mixture in the zone adjacent to each narrow gap zone on the downstream side. In addition, the inflow into each zone or the outflow from each zone may be a mixture that enters or leaves each zone, and for example, the outflow is not limited to one in which a discharge flow path to the outside of the extruder is provided in advance in the extruder configuration.

[0033] For each narrow gap zone, the pressure of the effluent from the narrow gap zone may, in one embodiment, be 0 MPa or more, or 0.001 MPa or more, or 0.01 MPa or more, and, in one embodiment, may be 4 MPa or less, or 2 MPa or less, or 1 MPa or less.

[0034] Second Embodiment The second embodiment provides a method including a mixing step of mixing a first component and a second component by an extruder having a mixing zone including a pressure drop zone. The method according to the second embodiment has the following features, but other than the features, it can be combined with one or more of the features exemplified above in relation to the first embodiment.

[0035] The pressure drop zone is a region in which the pressure of the inflow into the pressure drop zone is 0.5-20 MPa, and the ratio of the pressure of the outflow from the pressure drop zone to the pressure of the inflow into the pressure drop zone is 0.2 or less.

[0036] The pressure of the inflow into the pressure drop zone is preferably 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more from the viewpoint of favorably proceeding with the micronization of the second component, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less from the viewpoint of suppressing damage to the second component. Note that, in one embodiment, the pressure of the inflow into the pressure drop zone is substantially equal to the pressure of the mixture in the pressure drop zone.

[0037] In one embodiment, the content of the second component in the inflow to the pressure drop zone is 15 to 90% by mass, and / or the mixture is cooled in the compounding step by adding an additional polymer having a lower temperature than the mixture after passing through the pressure drop zone.

[0038] In a particular embodiment, the influent to the pressure drop zone has a second component content of 15-90 wt. %, the influent to the pressure drop zone has a pressure of 0.5-20 MPa, and the ratio of the pressure of the effluent from the pressure drop zone to the pressure of the influent to the pressure drop zone is 0.2 or less.

[0039] In a particular embodiment, the pressure of the influent into the pressure drop zone is 0.5 to 20 MPa, the ratio of the pressure of the effluent from the pressure drop zone to the pressure of the influent into the pressure drop zone is 0.2 or less, and in the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through the pressure drop zone to cool the mixture.

[0040] Referring to FIG. 2, in the second embodiment, the extruder 200 includes a kneading zone 201 and may optionally include a melting zone 202. For example, the method according to the second embodiment may further include a step of obtaining a premix by adding a second component a2 to a melt obtained by melting a first component a1 in a melting zone 202 before the kneading step in the kneading zone 201, and the premix may be supplied to the kneading zone 201. In normal kneading using an extruder, a strong shear is applied to the mixture in the first melting zone, so that when the second component is added to the molten resin from an addition port (side feeder) after the resin, which is the first component, passes through the melting zone, thermal degradation of the second component can be suppressed. The mixture is kneaded in the kneading zone 201 and taken out as a resin composition b.

[0041] The kneading zone 201 in the second embodiment includes a pressure drop zone D1. Although Fig. 2 shows an example in which one pressure drop zone D1 exists, in the second embodiment, the number of pressure drop zones may be selected according to the purpose, and in one aspect, the number is 1 or more, or 2 or more, or 3 or more, and in one aspect, the number is 10 or less, or 5 or less.

[0042] In one aspect, the pressure drop zone in the second embodiment may be the narrow gap zone described in the first embodiment. The cylinder gap of the narrow gap zone may be the same as that exemplified in the first embodiment. The pressure drop zone may be formed by adjusting one or more selected from the group consisting of the zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, screw speed, feed rate, resin composition, and void volume ratio of the present disclosure.

[0043] Third Embodiment 3 is a diagram illustrating the steps of the method for producing a resin composition according to the third embodiment. The method according to the third embodiment has the following characteristics, but other than these characteristics, one or more of the characteristics exemplified above for the first or second embodiment can be combined.

[0044] Referring to Fig. 3, in the third embodiment, an extruder 300 includes a kneading zone 301 and may optionally include a melting zone 302. For example, the method of the third embodiment may further include a step of obtaining a premixture by adding a second component a2, for example by side feeding, to a melt obtained by melting a first component a1 in a melting zone 202 before the kneading step in the kneading zone 301, and the premixture may be supplied to the kneading zone 301. Such an addition mode is preferable from the viewpoint of suppressing thermal degradation of the second component. The mixture is kneaded in the kneading zone 301 and taken out as a resin composition b.

[0045] In one embodiment, the kneading zone 301 includes a plurality of high pressure zones H1, H2, and H3 having a pressure of 0.1 MPa or more. Although Fig. 3 shows an example in which there are three high pressure zones, the number of high pressure zones in the kneading zone may be selected according to the purpose, and may be, for example, 2 or more, or 3 or more, and may be, for example, 10 or less, or 5 or less.

[0046] The ratio [P1 / P2] of the pressure [P1] (hereinafter also simply referred to as [P1]) of the highest pressure zone among the multiple high pressure zones H1, H2, H3, which has the highest pressure, to the average pressure [P2] of the pressures of the high pressure zones other than the highest pressure zone, in one embodiment, is greater than 1, or 1.5 or more, or 2 or more, from the viewpoint of favorably progressing the micronization of the second component, and in one embodiment, is 100 or less, or 50 or less, or 20 or less, from the viewpoint of suppressing damage to the second component. Note that the above average value [P2] means the pressure value of the relevant zone if there is one relevant zone, and means the arithmetic average of the pressure values ​​of the relevant zones if there are two or more relevant zones.

[0047] The ratio [P1 / P3] of [P1] to the pressure [P3] of each high pressure zone other than the highest pressure zone is, in one embodiment, greater than 1, or 1.5 or more, or 2 or more, from the viewpoint of smoothly progressing the micronization of the second component, and, in one embodiment, is 100 or less, or 50 or less, or 20 or less, from the viewpoint of suppressing damage to the second component.

[0048] In one embodiment, [P1] is 0.5 MPa or more, preferably 1 MPa or more, or 2 MPa or more, and preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.

[0049] [P2] is preferably 0.1 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, and preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.

[0050] [P3] is preferably 0.1 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, and preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.

[0051] The zone length / cylinder inner diameter ratio of each of the multiple high-pressure zones is, in one embodiment, 1 or more, or 2 or more, or 4 or more from the viewpoint of smoothly progressing the micronization of the second component, and, in one embodiment, is 30 or less, or 20 or less, or 15 or less from the viewpoint of suppressing damage to the second component.

[0052] The ratio of the zone length / cylinder inner diameter ratio of the highest pressure zone to the zone length / cylinder inner diameter ratio of each high pressure zone other than the highest pressure zone is, in one embodiment, 1 or more, or 2 or more, or 4 or more from the viewpoint of smoothly progressing the micronization of the second component, and, in one embodiment, is 30 or less, or 20 or less, or 15 or less from the viewpoint of suppressing damage to the second component.

[0053] The pressure in the highest pressure zone is, in one embodiment, 0.3 MPa or more, or 0.5 MPa or more, or 1 MPa or more from the viewpoint of smoothly progressing the micronization of the second component, and, in one embodiment, 50 MPa or less, or 20 MPa or less, or 15 MPa or less from the viewpoint of suppressing damage to the second component.

[0054] <Other Zones> Referring to Figures 1-3, the kneading zones 101, 201, 301 may have a dispersive mixing zone and a distributive mixing zone. The narrow gap zones N1, N2, N3, the pressure drop zone D1, and the high pressure zones H1, H2, H3 are dispersive mixing zones. Meanwhile, each of the other zones 11, 12, 13, 14, 21, 22, 31, 32, 33, 34 may be a dispersive mixing zone or a distributive mixing zone. The kneading conditions of the other zones may be arbitrarily designed to be the same or different from each other as desired. In a preferred embodiment, the most downstream zone of the kneading zone is the other zone (for example, like the other zones 14, 22, 24 in Figures 1-3), and is preferably a distributive mixing zone.

[0055] <Addition of additional polymer> 1 to 3, in the method according to embodiment A, an additional polymer, the same or different, preferably the same, as the polymer in the mixture, may be added (e.g., side-fed) to the mixture in the kneading zones 101, 201, 301. In a typical embodiment, the addition position of the additional polymer may be downstream of all narrow gap zones N1, N2, N3 in the kneading zone 101, downstream of the pressure drop zone D1 in the kneading zone 201, and downstream of all high pressure zones H1, H2, H3 in the kneading zone 301.

[0056] The amount of additional polymer added may be determined depending on the kneading conditions, the concentration of the desired second component in the resin composition, etc., and may be, for example, 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more, and 1,000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less, relative to 100 parts by mass of the mixture. In one embodiment, the concentration of the second component in the mixture before the addition of the additional polymer may be 10% by weight or more, or 15% by weight or more, or 20% by weight or more, or 25% by weight or more, or 30% by weight or more, and / or 90% by weight or less, or 80% by weight or less, or 70% by weight or less, or 60% by weight or less, or 50% by weight or less, and the concentration of the second component in the mixture after the addition of the additional polymer (which in one embodiment is equal to the concentration of the second component in the resin composition) may be 1% by weight or more, or 2% by weight or more, or 3% by weight or more, or 5% by weight or more, and / or 50% by weight or less, or 40% by weight or less, or 30% by weight or less, or 20% by weight or less.

[0057] (Cooling with additional polymer) The additional polymer may be at a lower temperature than the mixture. That is, in the kneading step, an additional polymer at a lower temperature than the mixture may be added to the mixture after passing through all of the multiple narrow gap zones according to the first embodiment, or the pressure drop zone (all of them in one embodiment when multiple zones are present) according to the second embodiment, or all of the multiple high pressure zones according to the third embodiment, to cool the mixture. The temperature of the additional polymer added for cooling is, in one embodiment, 0°C or higher, or 10°C or higher, or 20°C or higher, and in one embodiment, 300°C or lower, or 200°C or lower, or 100°C or lower, or 50°C or lower. The temperature of the mixture to which the additional polymer is added is, in one embodiment, 100°C or higher, or 150°C or higher, or 200°C or higher, and in one embodiment, 450°C or lower, or 400°C or lower, or 350°C or lower.

[0058] <Changes in flexural modulus> In the method according to aspect A, the flexural modulus improvement rate per unit mass of the mixture in each of the high-load zones (i.e., the ratio of the flexural modulus of the outflow from each zone to the flexural modulus of the inflow into each zone) is greater than the maximum value of the flexural modulus improvement rate per unit mass of the mixture in each zone other than the high-load zone (i.e., the ratio of the flexural modulus of the outflow from each zone to the flexural modulus of the inflow into each zone). In this case, the flexural modulus improvement effect in each high-load zone is good, while damage to the second component can be suppressed in other zones.

[0059] <Changes in thixotropy index> In the method according to aspect A, the ratio of the thixotropy index of the effluent from the kneading zone to the thixotropy index of the influent to the kneading zone is preferably 1 or more, or 2 or more, or 3 or more, from the viewpoint of uniform and fine dispersion of the second component by the kneading zone, and is preferably 100 or less, or 50 or less, or 10 or less, from the viewpoint of suppressing damage to the second component.

[0060] [Aspect B] The method according to Aspect B of the present disclosure includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder. The method according to Aspect B has the following features, but may otherwise combine one or more of the features exemplified above with respect to Aspect A. In one embodiment, the dispersive mixing zone according to Aspect B may comprise a high load zone according to Aspect A (more specifically, a narrow gap zone, a pressure drop zone, or a high pressure zone).

[0061] [1] A method for producing a resin composition containing a first component and a second component, comprising: The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The dispersive mixing zone includes a first dispersive mixing zone and a second dispersive mixing zone, which are different from each other in one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume rate; an increment [E1] of the tensile elongation of the outflow from the first dispersive mixing zone relative to the tensile elongation of the inflow to the first dispersive mixing zone, and an increment [E2] of the tensile elongation of the outflow from the second dispersive mixing zone relative to the tensile elongation of the inflow to the second dispersive mixing zone satisfy the relationship [E1]>[E2]; A method in which an increment [M1] in the bending modulus of an output from the first dispersive mixing zone relative to the bending modulus of an influent into the first dispersive mixing zone and an increment [M2] in the bending modulus of an output from the second dispersive mixing zone relative to the bending modulus of an influent into the second dispersive mixing zone satisfy the relationship [M1]<[M2]. [2] The method of claim 1, wherein the first dispersive mixing zone and the second dispersive mixing zone are in direct communication with each other, with the first dispersive mixing zone being upstream. [3] The method of claim 1, wherein the first dispersive mixing zone and the second dispersive mixing zone are in direct communication with each other, such that the second dispersive mixing zone is upstream. [4] The second component includes organic fibers, and the mass ratio of the organic fibers in the inflow to the first dispersing and mixing zone having a diameter of 50 μm or more is 10% to 90%, a ratio (1b / 1a) of a mass ratio (1a) of components having a diameter of 50 μm or more in the organic fibers in the inflow to the first dispersing and mixing zone to a mass ratio (1b) of components having a diameter of 50 μm or more in the organic fibers in the outflow from the first dispersing and mixing zone is 0 to 0.6; The method according to any one of the above-mentioned aspects 1 to 3, wherein the ratio (2b / 2a) of the mass ratio (2a) of components having a diameter of 50 μm or more in the organic fibers in the inflow to the second dispersing and mixing zone is 0.6 to 1. [5] The method according to any one of the above aspects 1 to 4, wherein the [E1] is 1% to 100%, the [E2] is 0% to 10%, the [M1] is 0 GPa to 1 GPa, the [M2] is 0.1 GPa to 20 GPa, the absolute value of the difference between the [E1] and [E2] is 0.1% to 100%, and the absolute value of the difference between the [M1] and [M2] is 0.1 GPa to 20 GPa. [6] The method according to any one of Aspects 1 to 5 above, wherein the first dispersing and mixing zone and the second dispersing and mixing zone each have a zone length / cylinder inner diameter ratio of 1 to 30. [7] The method according to any one of Aspects 1 to 6, wherein the mixture filling rate of each of the first dispersing and mixing zone and the second dispersing and mixing zone is 10% to 100%. [8] The method according to any one of Aspects 1 to 7 above, wherein the temperature of each of the first dispersing and mixing zone and the second dispersing and mixing zone is 100°C to 400°C. [9] The method according to any one of Aspects 1 to 8, wherein the mixed pressure in each of the first dispersing and mixing zone and the second dispersing and mixing zone is 0 MPa to 15 MPa.

[10] A method for producing a resin composition containing a first component and a second component, comprising: The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The method comprises varying one or more of the following in the cylinder length direction in the dispersion mixing zone: zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, and void volume ratio, thereby varying the ratio [ΔE / ΔM] of the change in tensile elongation ΔE (%) per value (l / d) obtained by dividing the progression length l (mm) of the mixture in the cylinder by the cylinder inner diameter d (mm) to the change in flexural modulus ΔM (GPa) per l / d in the cylinder length direction.

[11] The method according to claim 10, wherein the ratio [ΔE / ΔM] is gradually decreased from the upstream side to the downstream side of the cylinder.

[12] The method according to claim 10, wherein the ratio [ΔE / ΔM] is gradually increased from the upstream side to the downstream side of the cylinder.

[13] The method according to any one of Aspects 1 to 12 above, wherein the second component comprises organic fibers, preferably cellulose fibers, and the organic fibers in the resin composition have an average fiber diameter of 1000 nm or less and an average fiber length / average fiber diameter ratio of 30 or more.

[14] The method according to any one of Aspects 1 to 13, further comprising, prior to the dispersive mixing step, a step of adding the second component to a melt of the first component to obtain a premix, and supplying the premix to the dispersive mixing zone.

[0062] In the method of embodiment B, a region for mainly improving the tensile elongation (also referred to as a tensile elongation improving region in this disclosure) and a region for mainly improving the flexural modulus (also referred to as a flexural modulus improving region in this disclosure) are provided in the dispersion and mixing zone. In the tensile elongation improving region, the coarse aggregates of the second component are pulverized, thereby increasing the tensile elongation of the mixture, while the pulverization of the coarse aggregates contributes little to increasing the flexural modulus (i.e., stiffness) of the mixture. On the other hand, in the flexural modulus improving region, the second component is finely dispersed in the first component, thereby increasing the flexural modulus of the mixture, while the fine dispersion contributes little to increasing the tensile elongation of the mixture.

[0063] In the method of aspect B, the tensile elongation and the flexural modulus are not increased simultaneously, but one of the tensile elongation and the flexural modulus is preferentially increased in each of the tensile elongation-improving region and the flexural modulus-improving region. Unexpectedly, the resin composition obtained through such a process can achieve high and stable compatibility of the tensile elongation and the flexural modulus, compared with the resin composition obtained through the process that attempts to increase the tensile elongation and the flexural modulus simultaneously. The above advantage can be remarkable when the second component contains organic fibers, particularly cellulose fibers. Aspect B more specifically includes the following first and second embodiments.

[0064] First Embodiment FIG. 4 is a diagram for explaining the steps of the method for producing a resin composition according to the first embodiment, and FIG. 5 is a diagram for explaining the change behavior of the tensile elongation and flexural modulus in the method according to the first embodiment. Referring to FIG. 4, in the first embodiment, the extruder 400 has a dispersive mixing zone 401. The extruder 400 may further have a distributive mixing zone 402. The extruder 400 may also have a melting zone 403 upstream of the dispersive mixing zone 401, and / or a melting zone 404 downstream of the dispersive mixing zone 401. For example, the method of the present disclosure may further include a step of adding a second component a2 to a melt obtained by melting a first component a1 in the melting zone 403 to obtain a premix before the dispersive mixing step in the dispersive mixing zone 401, and the premix may be supplied to the dispersive mixing zone 401. In normal kneading using an extruder, the mixture is subjected to strong shear in the first melting zone, so when the second component is added to the molten first component from an addition port (side feeder) after the resin has passed through the melting zone, thermal degradation of the second component can be suppressed. The mixture is dispersed and mixed and optionally distributed in the extruder 400, and is taken out as resin composition b.

[0065] In addition, the method according to the embodiment B may further include a step of adding an additional polymer, which is the same or different, preferably the same, as the first component in the dispersive mixing product, to the dispersive mixing product after the dispersive mixing step and before the dispersive mixing step to obtain an additional polymer mixture, and the additional polymer mixture may be supplied to the dispersive mixing zone. For example, the additional polymer may be added to the outflow from the dispersive mixing zone 401 (for example, by side-feeding the additional polymer in the melting zone 404 in FIG. 4), and then supplied to the dispersive mixing zone 402. The amount of the additional polymer added may be determined depending on the kneading conditions, the desired concentration of the second component in the resin composition, and the like, and may be, for example, 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more, and 1000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less, relative to 100 parts by mass of the dispersive mixing product. In one embodiment, the concentration of the second component in the dispersed mixture product may be 10% by weight or more, or 20% by weight or more, or 25% by weight or more, or 30% by weight or more, and / or 80% by weight or less, or 70% by weight or less, or 60% by weight or less, or 50% by weight or less, and the concentration of the second component in the additional polymer mixture (which in one embodiment is equal to the concentration of the second component in the resin composition) may be 1% by weight or more, or 2% by weight or more, or 3% by weight or more, or 5% by weight or more, and / or 50% by weight or less, or 40% by weight or less, or 30% by weight or less, or 20% by weight or less.

[0066] (Cooling with additional polymer) The additional polymer may be at a lower temperature than the dispersed blend product, thereby cooling the dispersed blend product. The temperature of the additional polymer added for cooling is, in one embodiment, 0° C. or more, or 10° C. or more, or 20° C. or more, and in one embodiment, 300° C. or less, or 200° C. or less, or 100° C. or less, or 50° C. or less. The temperature of the dispersed blend product to which the additional polymer is added is, in one embodiment, 100° C. or more, or 150° C. or more, or 200° C. or more, and in one embodiment, 450° C. or less, or 400° C. or less, or 350° C. or less.

[0067] The dispersive mixing zone 401 includes a first dispersive mixing zone 41 and a second dispersive mixing zone 42 having different process conditions. In one embodiment, the first dispersive mixing zone 41 and the second dispersive mixing zone 42 are directly connected to each other. In one embodiment, an additional dispersive mixing zone may be present upstream of the first dispersive mixing zone 41, between the first dispersive mixing zone 41 and the second dispersive mixing zone 42, and / or downstream of the second dispersive mixing zone 42. For example, a third dispersive mixing zone (not shown) having the same or different configuration as the first dispersive mixing zone 41 or the second dispersive mixing zone 42 may be disposed downstream of the second dispersive mixing zone 42, and an outflow from the third dispersive mixing zone may be recovered as the resin composition b.

[0068] In one embodiment, the process conditions are one or more selected from the group consisting of zone length / cylinder inner diameter ratio, mixture packing rate, temperature, pressure, and void volume fraction.

[0069] The above-mentioned zone length refers to the total length of the screw elements constituting the dispersive mixing zone and the distributive mixing zone, and depends on the screw configuration.

[0070] The mixture filling rate is the ratio of the actual amount of the mixture filled (by volume) to the space volume of the extruder, and is calculated by a method in which the screw rotation and the supply of the raw material are suddenly stopped, the screw is pulled out, the mixture adhering to the screw surface is sampled and weighed, and the volume of the filled mixture is calculated by dividing it by the density of the mixture, and then the volume of the filled mixture is divided by the space volume described below to calculate the mixture filling rate. The mixture filling rate depends on the screw configuration and the extrusion conditions.

[0071] The space volume ratio is calculated by subtracting the screw volume (the total of the element volume and the shaft volume) from the cylinder volume of the extruder to calculate the space volume, and then dividing the space volume by the cylinder volume. The space volume ratio depends on the screw configuration.

[0072] 4 and 5, the increment [E1] of the tensile elongation of the outflow 41b from the first dispersive mixing zone relative to the tensile elongation of the inflow 41a into the first dispersive mixing zone and the increment [E2] of the tensile elongation of the outflow 42b from the second dispersive mixing zone relative to the tensile elongation of the inflow 42a into the second dispersive mixing zone satisfy the relationship [E1]>[E2]. Also, the increment [M1] of the flexural modulus of the outflow 41b from the first dispersive mixing zone relative to the flexural modulus of the inflow 41a into the first dispersive mixing zone and the increment [M2] of the flexural modulus of the outflow 42b from the second dispersive mixing zone relative to the flexural modulus of the inflow 42a into the second dispersive mixing zone satisfy the relationship [M1]<[M2]. That is, the first dispersive mixing zone is a tensile elongation improving region, and the second dispersive mixing zone is a flexural modulus improving region.

[0073] In one embodiment, as shown in Fig. 4, the first dispersing and mixing zone 41 and the second dispersing and mixing zone 42 are in communication (direct communication in one embodiment) with the first dispersing and mixing zone 41 located upstream. Such an arrangement is advantageous in terms of further improving the elastic modulus.

[0074] On the other hand, in another embodiment, the first and second dispersing and mixing zones may be connected (directly connected in one embodiment) so that the second dispersing and mixing zone is located upstream. Such an arrangement is advantageous in terms of further improving elongation.

[0075] In addition, the inflow to each zone or the outflow from each zone may be any mixture that enters or leaves each zone, and for example, the outflow is not limited to an extruder configuration in which a discharge flow path to the outside of the extruder is already provided.

[0076] In one embodiment where the second component includes organic fibers, the mass ratio of the organic fibers having a diameter of 50 μm or more in the inflow 41a to the first dispersing and mixing zone is preferably 10% or more, or 20% or more, or 30% or more, or 40% or more, and preferably 90% or less, or 80% or less, or 70% or less, or 60% or less. That is, the inflow 41a may include a significant amount of coarse particles.

[0077] In one embodiment, the ratio (1b / 1a) of the mass ratio (1b) of the components having a diameter of 50 μm or more in the organic fibers in the inflow 41a to the first dispersing and mixing zone to the mass ratio (1a) of the components having a diameter of 50 μm or more in the organic fibers in the outflow 41b from the first dispersing and mixing zone is preferably 0 or more, or 0.1 or more, or 0.2 or more, and preferably 0.6 or less, or 0.5 or less, or 0.3 or less. In this case, coarse particles are pulverized in the first dispersing and mixing zone 41, and the number of coarse particles in the outflow 41b is significantly reduced.

[0078] In one embodiment, the ratio (2b / 2a) of the mass ratio (2b) of the components having a diameter of 50 μm or more in the organic fibers in the inflow 42a to the second dispersing and mixing zone is preferably 0.6 or more, or 0.7 or more, or 0.8 or more, and preferably 1 or less, or 0.9 or less. In this case, while fine dispersion progresses in the second dispersing and mixing zone 42, the reduction of coarse particles from the inflow 42a to the outflow 42b is slight. In this disclosure, when the mass ratios (2a) and (2b) are both 0%, the ratio (2b / 2a) is treated as 1.

[0079] In one embodiment, [E1] is preferably 1% or more, or 2% or more, or 3% or more, and preferably 100% or less, or 50% or less, or 30% or less; [E2] is preferably 0% or more, and preferably 10% or less, or 5% or less, or 3% or less; [M1] is preferably 0 GPa or more, or 0.1 GPa or more, or 0.3 GPa or more, and preferably 1 GPa or less, or 0.7 GPa or less, or 0.5 GPa or less; [M2] is preferably 0.1 GPa or more, or is 0.5 GPa or more, or 1 GPa or more, and preferably 20 GPa or less, or 10 GPa or less, or 5 GPa or less, the absolute value of the difference between [E1] and [E2] is preferably 0.1% or more, or 1% or more, or 5% or more, and preferably 100% or less, or 50% or less, or 30% or less, and the absolute value of the difference between [M1] and [M2] is preferably 0.1 GPa or more, or 0.5 GPa or more, or 1 GPa or more, and preferably 20 GPa or less, or 10 GPa or less, or 5 GPa or less.

[0080] In one embodiment, the zone length / cylinder inner diameter ratio of each of the first and second dispersive mixing zones is preferably 1 or more, or 3 or more, or 4 or more, and preferably 30 or less, or 20 or less, or 10 or less.

[0081] In one embodiment, the mixture fill factor of each of the first and second dispersive mixing zones is preferably 10% or more, or 50% or more, or 70% or more, and preferably 100% or less, or 99% or less, or 95% or less.

[0082] In one embodiment, the temperature of each of the first and second dispersive mixing zones is preferably 100°C or more, or 150°C or more, or 200°C or more, and preferably 400°C or less, or 350°C or less, or 300°C or less.

[0083] In one embodiment, the mixed pressure in each of the first and second dispersive mixing zones is preferably 0 MPa or more, or 0.1 MPa or more, or 0.3 MPa or more, or 1 MPa or more, and preferably 15 MPa or less, or 10 MPa or less, or 5 MPa or less, or 3 MPa or less.

[0084] In one embodiment, the void volume fraction of each of the first and second dispersive mixing zones is preferably 10% or more, or 20% or more, or 30% or more, and preferably 70% or less, or 60% or less, or 50% or less.

[0085] The resin composition dispersed and mixed in the dispersive mixing zone 401 may be introduced into the distributive mixing zone 402 via or without passing through other zones (e.g., the melting zone 404) and further dispersed and mixed. The mixing conditions in the distributive mixing zone are not particularly limited, but distributive mixing may be performed, for example, by arbitrarily combining kneading disks such as a forward kneading disk and a neutral kneading disk.

[0086] Second Embodiment Fig. 6 is a diagram for explaining the steps of the method for producing a resin composition according to the second embodiment, and Fig. 7 is a diagram for explaining the change behavior of the tensile elongation and flexural modulus in the method according to the second embodiment. The method according to the second embodiment has the following characteristics, but other than the characteristics, the same procedures and conditions as those described above for the first embodiment may be appropriately adopted.

[0087] Referring to FIG. 6, in the second embodiment, the extruder 600 has a dispersive mixing zone 601, and may further have a distributive mixing zone 602, a melting zone 603 upstream of the dispersive mixing zone 601, and / or a melting zone 604 downstream of the dispersive mixing zone 601. For example, the method according to the aspect B may further include a step of adding a second component a2 to a melt obtained by melting a first component a1 in the melting zone 603 to obtain a premix before the dispersive mixing step in the dispersive mixing zone 601, and the premix may be supplied to the dispersive mixing zone 601. When the second component a2 is added to the first component in a molten state from an addition port (side feeder) after the first component a1 passes through the melting zone 603, it is preferable because the thermal degradation of the second component can be suppressed. The mixture is dispersively mixed and optionally distributively mixed in the extruder 600, and taken out as a resin composition b.

[0088] 6 and 7, the dispersive mixing zone 601 has different process conditions, which change the ratio [ΔE / ΔM] of the change in tensile elongation ΔE (%) per value (l / d) obtained by dividing the progression length l of the mixture in the cylinder (i.e., the flow length in the cylinder length direction L when the mixture flows through the dispersive mixing zone 601) (mm) by the cylinder inner diameter d (mm) to the change in flexural modulus ΔM (GPa) per l / d in the cylinder length direction L. In one embodiment, the process condition is one or more selected from the group consisting of the zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, and void volume rate.

[0089] In one embodiment, the ratio [ΔE / ΔM] is gradually decreased from the upstream side to the downstream side of the cylinder. In such an embodiment, the upstream side of the cylinder corresponds to the tensile elongation improvement region, and the downstream side corresponds to the flexural modulus improvement region, which is advantageous in that a resin composition with higher rigidity can be obtained. In this embodiment, ΔE may gradually decrease and ΔM may gradually increase from the upstream side to the downstream side of the cylinder. For example, from the inlet to the outlet of the dispersive mixing zone 601, ΔE may decrease from a range of 0.1% or more, or 1% or more, or 10% or more and 300% or less, or 200% or less, or 100% or less to a range of 0.01% or more, or 0.1% or more, or 0.5% or more and 10% or less, or 5% or less, or 2% or less, and ΔM may increase from a range of 0.001 GPa or more, or 0.01 GPa or more, or 0.05 GPa or more and 10 GPa or less, or 5 GPa or less, or 2 GPa or less to a range of 0.02 GPa or more, or 0.05 GPa or more, or 0.1 GPa or more and 50 GPa or less, or 10 GPa or less, or 5 GPa or less.

[0090] On the other hand, in another embodiment, the ratio [ΔE / ΔM] is gradually increased from the upstream side to the downstream side of the cylinder. In such an embodiment, the upstream side of the cylinder corresponds to the bending modulus improvement region, and the downstream side corresponds to the tensile elongation improvement region, which is advantageous in that a resin composition with higher elongation can be obtained. In this embodiment, ΔE may gradually increase and ΔM may gradually decrease from the upstream side to the downstream side of the cylinder. For example, from the inlet to the outlet of the dispersive mixing zone, ΔE may increase from a range of 0.01% or more, or 0.1% or more, or 0.5% or more and 10% or less, or 5% or less, or 2% or less to a range of 0.1% or more, or 1% or more, or 10% or more and 300% or less, or 200% or less, or 100% or less, and ΔM may decrease from a range of 0.02 GPa or more, or 0.05 GPa or more, or 0.1 GPa or more and 50 GPa or less, or 10 GPa or less, or 5 GPa or less to a range of 0.001 GPa or more, or 0.01 GPa or more, or 0.05 GPa or more and 10 GPa or less, or 5 GPa or less, or 2 GPa or less.

[0091] <<Aspect C>> The method according to aspect C of the present disclosure includes a dispersive mixing step of dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder to obtain a dispersively mixed product, and a distributive mixing step of distributively mixing at least the dispersively mixed product in a distributive mixing zone of the extruder to obtain a resin composition. The method according to aspect C has the following characteristics, but other than these characteristics, one or more of the characteristics exemplified above for aspect A can be combined. In one embodiment, the dispersive mixing zone according to aspect C may include a high load zone according to aspect A (more specifically, a narrow gap zone, a pressure drop zone, or a high pressure zone). [1] A method for producing a resin composition comprising a first component and a second component, the method comprising: a dispersive mixing step of dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The dispersive mixing zone and the distributive mixing zone are different from each other in at least one selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume ratio; an increment [EA] of the tensile elongation of the outflow from the dispersive mixing zone relative to the tensile elongation of the inflow to the dispersive mixing zone and an increment [EB] of the tensile elongation of the outflow from the distributive mixing zone relative to the tensile elongation of the inflow to the distributive mixing zone satisfy the relationship [EA]>[EB]; A method in which the increment [MA] of the bending modulus of the output from the dispersive mixing zone relative to the bending modulus of the influent to the dispersive mixing zone and the increment [MB] of the bending modulus of the output from the distributive mixing zone relative to the bending modulus of the influent to the distributive mixing zone satisfy the relationship [MA] > [MB]. [2] The method according to aspect 1, wherein the [EA] is 1% to 100%, the [EB] is 0% to 10%, the [MA] is 0.1 GPa to 20 GPa, the [MB] is 0 GPa to 1 GPa, the difference between [EA] and [EB] ([EA]-[EB]) is 0.01% to 100%, and the difference between [MA] and [MB] ([MA]-[MB]) is 0.001 GPa to 10 GPa. [3] The method according to any one of the first to second aspects, wherein the mixed pressure is 0.3 MPa or more in a region in which the zone length / cylinder inner diameter ratio of the dispersive mixing zone is 1 or more and the zone length / cylinder inner diameter ratio of the distributive mixing zone is 5 or less. [4] A method for producing a resin composition comprising a first component and a second component, the method comprising: a dispersive mixing step of dispersively mixing the cellulose fibers and the resin in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The method wherein the concentration of the second component in the dispersive mixing zone [CA] is 10% by mass to 90% by mass, the concentration of the second component in the distributive mixing zone [CB] is 1% by mass to 50% by mass, and the ratio [CA] / [CB] is 2-90. [5] A method according to any one of the above aspects 1 to 4, wherein the increment [TA] of the thixotropy index of the effluent from the dispersive mixing zone relative to the thixotropy index of the influent to the dispersive mixing zone and the increment [TB] of the thixotropy index of the effluent from the distributive mixing zone relative to the thixotropy index of the influent to the distributive mixing zone satisfy the relationship [TA]>[TB]. [6] The method according to claim 5, wherein the [TA] is greater than 0.01 and less than 10, the [TB] is greater than 0.01 and less than 10, and the [TA] / [TB] ratio is greater than 1 and less than 100. [7] The method according to any one of the above aspects 1 to 6, wherein the property improvement rate per unit mass of the second component in the mixture is greater in the distributive mixing zone than in the dispersive mixing zone. [8] The method of any one of Aspects 1 to 7, further comprising the step of adding an additional polymer to the dispersively mixed product after the dispersive mixing step and before the distributive mixing step to obtain an additional polymer mixture, and feeding the additional polymer mixture to the distributive mixing zone. [9] The method according to any one of the above aspects 1 to 8, wherein the second component comprises organic fibers, preferably cellulose fibers, and the organic fibers in the resin composition have an average fiber diameter of 1000 nm or less and an average fiber length / average fiber diameter ratio of 30 or more.

[0092] In the method of aspect C, the tensile elongation and flexural modulus are not increased through dispersive mixing and distributive mixing, but rather, during dispersive mixing, a relatively large force is applied to the second component to greatly improve the tensile elongation and flexural modulus of the mixture, while during distributive mixing, the mixing conditions are made gentle so that the force applied to the second component is minimized, so that the improvement in tensile elongation and flexural modulus is small but damage to the second component is avoided. In a molded article formed from a resin composition obtained through such process steps, unexpectedly, the tensile elongation and flexural modulus can be highly and stably achieved at the same time.

[0093] Fig. 8 is a diagram illustrating steps of a method for producing a resin composition according to one embodiment of the present invention. Referring to Fig. 8, an extruder 800 has a dispersive mixing zone 801 and a distributive mixing zone 802. In a typical embodiment, as shown in Fig. 8, the distributive mixing zone 802 is disposed downstream of the dispersive mixing zone 801. The extruder 800 may further have a melting zone 803 upstream of the dispersive mixing zone 801, and / or a melting zone 804 downstream of the dispersive mixing zone 801 and upstream of the distributive mixing zone 802.

[0094] The method according to embodiment C may further include a step of adding a second component a2 to a melt obtained by melting a first component a1 in a melting zone 803 to obtain a premix before the dispersive mixing step in the dispersive mixing zone 801, and the premix may be supplied to the dispersive mixing zone 801. In normal kneading using an extruder, strong shear is applied to the mixed material in the first melting zone, so when the second component is added to the molten first component from an addition port (side feeder) after the first component has passed through the melting zone, thermal degradation of the second component can be suppressed. The mixture is dispersively mixed and distributed in the extruder 800, and taken out as a resin composition b.

[0095] Also, the method according to embodiment C may further include a step of adding an additional polymer, the same or different, preferably the same, to the dispersively mixed product after the dispersive mixing step and before the dispersive mixing step, to obtain an additional polymer mixture, and the additional polymer mixture may be supplied to the dispersive mixing zone. For example, the additional polymer may be added to the outflow from the dispersive mixing zone 801 (for example, by side-feeding the additional polymer in the melting zone 804 in FIG. 8), and then supplied to the dispersive mixing zone 802. The amount of the additional polymer added may be determined depending on the kneading conditions, the desired concentration of the second component in the resin composition, and the like, and may be, for example, 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more, and 1000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less, relative to 100 parts by mass of the dispersively mixed product. In one embodiment, the concentration of the second component in the dispersed mixture product may be 10% by weight or more, or 20% by weight or more, or 25% by weight or more, or 30% by weight or more, and / or 80% by weight or less, or 70% by weight or less, or 60% by weight or less, or 50% by weight or less, and the concentration of the second component in the additional polymer mixture (which in one embodiment is equal to the concentration of the second component in the resin composition) may be 1% by weight or more, or 2% by weight or more, or 3% by weight or more, or 5% by weight or more, and / or 50% by weight or less, or 40% by weight or less, or 30% by weight or less, or 20% by weight or less.

[0096] (Cooling with additional polymer) The additional polymer may be at a lower temperature than the dispersed blend product, thereby cooling the dispersed blend product. The temperature of the additional polymer added for cooling is, in one embodiment, 0° C. or more, or 10° C. or more, or 20° C. or more, and in one embodiment, 300° C. or less, or 200° C. or less, or 100° C. or less, or 50° C. or less. The temperature of the dispersed blend product to which the additional polymer is added is, in one embodiment, 100° C. or more, or 150° C. or more, or 200° C. or more, and in one embodiment, 450° C. or less, or 400° C. or less, or 350° C. or less. Aspect C more specifically encompasses the following first and second embodiments.

[0097] First embodiment (process condition control) 8, in the first embodiment, the dispersive mixing zone 801 and the distributive mixing zone 802 have different process conditions. In one embodiment, the process conditions are one or more selected from the group consisting of zone length / cylinder inner diameter ratio, mixture packing rate, temperature, pressure, and void volume rate.

[0098] The above-mentioned zone length refers to the total length of the screw elements constituting the dispersive mixing zone and the distributive mixing zone, and depends on the screw configuration.

[0099] The mixture filling rate is the ratio of the actual amount of the mixture filled (by volume) to the space volume of the extruder, and is calculated by a method in which the screw rotation and the supply of the raw material are suddenly stopped, the screw is pulled out, the mixture adhering to the screw surface is sampled and weighed, and the volume of the filled mixture is calculated by dividing it by the density of the mixture, and then the volume of the filled mixture is divided by the space volume described below to calculate the mixture filling rate. The mixture filling rate depends on the screw configuration and the extrusion conditions.

[0100] The space volume ratio is calculated by subtracting the screw volume (the sum of the element volume and the shaft volume) from the barrel volume of the extruder to calculate the space volume, and then dividing the space volume by the barrel volume. The space volume ratio depends on the screw configuration.

[0101] In one embodiment, the increment [EA] of the tensile elongation of the effluent from the dispersive mixing zone 801 relative to the tensile elongation of the influent to the dispersive mixing zone 801 and the increment [EB] of the tensile elongation of the effluent from the dispersive mixing zone 802 relative to the tensile elongation of the influent to the dispersive mixing zone 802 satisfy the relationship [EA] > [EB], and the increment [MA] of the flexural modulus of the effluent from the dispersive mixing zone 801 relative to the flexural modulus of the influent to the dispersive mixing zone 801 and the increment [MB] of the flexural modulus of the effluent from the dispersive mixing zone 802 relative to the flexural modulus of the influent to the dispersive mixing zone 802 satisfy the relationship [MA] > [MB].

[0102] In addition, the inflow to each zone or the outflow from each zone may be any mixture that enters or leaves each zone, and for example, the outflow is not limited to an extruder configuration in which a discharge flow path to the outside of the extruder is already provided.

[0103] [EA] is preferably 1% or more, or 2% or more, or 3% or more, and preferably 100% or less, or 50% or less, or 30% or less. [EB] is preferably 0% or more, or 0.1% or more, or 0.5% or more, and preferably 10% or less, or 5% or less, or 3% or less.

[0104] [MA] is preferably 0.1 GPa or more, or 0.5 GPa or more, or 1 GPa or more, and preferably 20 GPa or less, or 10 GPa or less, or 5 GPa or less. [MB] is preferably 0 GPa or more, or 0.1 GPa or more, or 0.3 GPa or more, and preferably 1 GPa or less, or 0.7 GPa or less, or 0.5 GPa or less.

[0105] The difference between [EA] and [EB] ([EA] - [EB]) is preferably 0.01% or more, or 0.1% or more, or 1% or more, and preferably 100% or less, or 50% or less, or 10% or less.

[0106] The difference between [MA] and [MB] ([MA]-[MB]) is preferably 0.001 GPa or more, or 0.01 GPa or more, or 0.1 GPa or more, and preferably 10 GPa or less, or 5 GPa or less, or 1 GPa or less.

[0107] In one embodiment, the zone length / cylinder inner diameter ratio of each of dispersive mixing zone 801 and distributive mixing zone 802 is preferably 1 or more, or 3 or more, or 4 or more, and preferably 30 or less, or 20 or less, or 10 or less.

[0108] In one embodiment, the mixture filling rate of each of the dispersive mixing zone 801 and the distributive mixing zone 802 is preferably 10% or more, or 50% or more, or 70% or more, and preferably 100% or less, or 99% or less, or 95% or less.

[0109] In one embodiment, the temperature of each of dispersive mixing zone 801 and distributive mixing zone 802 is preferably 100°C or more, or 150°C or more, or 200°C or more, and preferably 400°C or less, or 350°C or less, or 300°C or less.

[0110] In one embodiment, the mixed pressure in each of the dispersive mixing zone 801 and the distributive mixing zone 802 is preferably 0 MPa or more, or 0.1 MPa or more, or 0.3 MPa or more, or 1 MPa or more, and preferably 15 MPa or less, or 10 MPa or less, or 5 MPa or less, or 3 MPa or less.

[0111] In one embodiment, the void volume ratio of each of the dispersive mixing zone 801 and the distributive mixing zone 802 is preferably 10% or more, or 20% or more, or 30% or more, and preferably 70% or less, or 60% or less, or 50% or less.

[0112] In one embodiment, in the region where the zone length / cylinder inner diameter ratio of the dispersive mixing zone 801 is 1 or more, or 2 or more, or 5 or more, and the zone length / cylinder inner diameter ratio of the distributive mixing zone 802 is 5 or less, or 2 or less, or 1 or less, the pressure of the mixture is 0.1 MPa or more, or 0.2 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more, or 5 MPa or more, or 7 MPa or more. From the viewpoint of suppressing damage to the second component, the pressure of the mixture may be preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less. In this case, the region where high pressure is applied to the mixture can be relatively wide in the dispersive mixing zone 801 and relatively narrow in the distributive mixing zone 802. As a result, the second component is finely divided well in the dispersive mixing zone 801, while the state of dispersion of the second component in the first component can be improved in the distributive mixing zone 802 while avoiding damage to the second component. The region where the mixed pressure is in the above range may be a region where the zone length / cylinder inner diameter ratio of the dispersive mixing zone 801 is 30 or less, or 20 or less, or 10 or less.

[0113] In one embodiment, in a region where the zone length / cylinder inner diameter ratio of the dispersive mixing zone is 1 or more, and the zone length / cylinder inner diameter ratio of the distributive mixing zone is 5 or less, the mixed pressure is 0.3 MPa or more.

[0114] In one embodiment, from the viewpoint of improving the dispersion of the second component and making it more practical, the improvement rate of the physical property per unit mass of the second component in the mixture is larger in the distributive mixing zone than in the dispersive mixing zone. The improvement rate of the physical property in the dispersive mixing zone is the ratio of the physical property of the outflow from the dispersive mixing zone to the physical property of the inflow into the dispersive mixing zone, and the improvement rate of the physical property in the distributive mixing zone is the ratio of the physical property of the outflow from the distributive mixing zone to the physical property of the inflow into the distributive mixing zone. In one embodiment, the physical property is selected from tensile elongation and flexural modulus. From the above viewpoint, the ratio of the improvement rate of the physical property in the distributive mixing zone to the dispersive mixing zone is preferably more than 1, or 1.2 or more, or 1.5 or more, and from the viewpoint of ease of designing process conditions, it may be, for example, 100 or less, 10 or less, or 5 or less.

[0115] Second embodiment (control of concentration of second component) Referring again to FIG. 8, in the second embodiment, the concentration [CA] of the second component in the dispersive mixing zone 801 is 10% by mass to 90% by mass, the concentration [CB] of the second component in the distributive mixing zone 802 is 1% by mass to 50% by mass, and the ratio [CA] / [CB] is 2 to 90. For example, the concentration of the second component can be adjusted to the above range by adding additional polymer to the outflow from the dispersive mixing zone 801 (for example, by side feeding additional polymer in the melting zone 804 in FIG. 8) and then supplying it to the distributive mixing zone 802. By adjusting the concentrations of the second component in the dispersive mixing zone 801 and the distributive mixing zone 802 as described above, it is possible to simultaneously achieve the refinement of the second component in the dispersive mixing zone 801 and the improvement of the dispersion state of the second component while avoiding damage to the second component in the distributive mixing zone 802.

[0116] In one embodiment, the concentration [CA] is 10% by mass or more, or 15% by mass or more, or 20% by mass or more from the viewpoint of smoothly proceeding with the micronization of the second component, and in one embodiment, the concentration [CA] is 90% by mass or less, or 80% by mass or less, or 70% by mass or less from the viewpoint of suppressing damage to the second component.

[0117] The above concentration [CB] is, in one aspect, 1 mass% or more, or 5 mass% or more, or 10 mass% or more from the viewpoint of adjusting the concentration of the second component in the resin composition according to various applications, and, in one aspect, 50 mass% or less, or 40 mass% or less, or 30 mass% or less from the viewpoint of suppressing damage to the second component.

[0118] The above ratio [CA] / [CB] is, in one aspect, 2 or more, or 3 or more, or 4 or more, from the viewpoint of promoting micronization in the dispersion mixing process of the second component and suppressing damage in the distribution mixing process, and, in one aspect, is 90 or less, or 50 or less, or 10 or less, from the viewpoint of avoiding damage to the second component due to too high a concentration [CA] or limitations on the application uses of the resin composition due to too low a concentration [CB].

[0119] <Changes in thixotropy index> In one embodiment, the increment [TA] of the thixotropy index of the effluent from the dispersive mixing zone 801 relative to the thixotropy index of the influent to the dispersive mixing zone 801 and the increment [TB] of the thixotropy index of the effluent from the dispersive mixing zone 802 relative to the thixotropy index of the influent to the dispersive mixing zone 802 satisfy the relationship [TA]>[TB]. A larger increment [TA] indicates that the second component has been finely divided in the dispersive mixing zone 801, and a larger increment [TB] indicates that the second component has been finely divided in the dispersive mixing zone 802. [TA]>[TB] is an indicator that the second component is preferentially finely divided in the dispersive mixing zone 801 rather than in the distributive mixing zone 802.

[0120] The [TA] / [TB] ratio is preferably more than 1, or 2 or more, or 3 or more, from the viewpoint of preferentially finely dispersing the second component in the dispersing and mixing zone 801, and is preferably 100 or less, or 50 or less, or 10 or less, from the viewpoint of suppressing damage to the second component due to excessive finely dispersing the second component in the dispersing and mixing zone 801. The method for measuring the thixotropy index will be described later.

[0121] The increment [TA] is preferably greater than 0.01 and equal to or less than 10, or from 0.05 to 5, or from 0.1 to 2. The increment [TB] is preferably 0.01 or more and less than 10, or 0.05 to 5, or 0.1 to 2.

[0122] [Extrusion of resin composition] In the methods according to the aspects A to C, the resin composition b that has left the kneading zone 101, 201, 301 (for aspect A), the distributive mixing zone 402, 602 (for aspect B), or the distributive mixing zone 802 (for aspect C) may be extruded out of the extruder in a desired shape. For example, a pellet shape is preferable from the viewpoint of ease of post-processing and transportation. Suitable examples of the pellet shape include a round shape, an elliptical shape, a cylindrical shape, and the like, and differ depending on the cutting method during extrusion processing. Examples of the size of the round pellets include a diameter of 1 mm or more and 3 mm or less, and examples of the size of the cylindrical pellets include a diameter of 1 mm or more and 3 mm or less, and a length of 2 mm or more and 10 mm or less. It is desirable to set the above diameter and length to the lower limit or more from the viewpoint of operational stability during extrusion, and it is desirable to set them to the upper limit or less from the viewpoint of bite into the molding machine during post-processing.

[0123] [Production of Molded Products] The resin composition produced by the method according to the aspects A to C may be molded into a molded article having various forms such as a film, a sheet, a fiber, a plate, a powder, or a three-dimensional structure. Examples of the molding method include injection molding, extrusion molding, foam molding, insert molding, in-mold coating molding, and mold molding. For example, various extrusion moldings are suitable for molding sheets, films, fibers, and the like. The molding temperature can be appropriately selected depending on the composition of the resin composition, and may be, for example, the melting point of the resin used or higher, or the melting point + 20°C or higher, or the melting point + 30°C or higher, and may be the melting point + 90°C or lower, the melting point + 80°C or lower, or the melting point + 70°C or lower.

[0124] [Material components of resin composition] The resin composition produced by the method according to the present disclosure, particularly according to aspects A to C, includes a first component which is a polymer, and a second component which is an organic fiber and / or a polymer different from the first component. In one embodiment, the polymer different from the first component means a polymer having a molecular structure and / or a molecular weight different from that of the first component. The polymer in the first component, the organic fiber in the second component, and the polymer in the second component may each be one type or two or more types. In one embodiment, the polymer in the first component and the polymer in the second component are different from each other in the molecular structure and / or molecular weight of at least one polymer constituting them. In one embodiment, the second component is an organic fiber, a polymer, and a combination of an organic fiber and a polymer. Examples of material components used to produce the resin composition and therefore contained in the resin composition include the following.

[0125] <First ingredient> In one embodiment, the first component is a polymer. The polymer is appropriately selected depending on the intended use of the resin composition, and may be, for example, a crystalline thermoplastic resin having a melting point within the range of 100°C to 350°C, or an amorphous thermoplastic resin having a glass transition point within the range of 100°C to 250°C. Examples of the polymer include polyolefin resins, polyamide resins, polyester resins, polyacetal resins, polyphenylene ether resins, polyphenylene sulfide resins, and mixtures of two or more of these. From the viewpoint of handling and cost, preferred are polyolefin resins, polyamide resins, polyester resins, polyacetal resins, etc., more preferred are polyamide resins, polyolefin resins, and polyacetal resins, and particularly preferred are polyamide resins and polyacetal resins. From the viewpoint of enhancing the heat resistance of the resin composition, the melting point of the thermoplastic resin (particularly the crystalline resin) is preferably 140°C or more, or 150°C or more, or 160°C or more, or 170°C or more, or 180°C or more, or 190°C or more, or 200°C or more, or 210°C or more, or 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more.

[0126] The melting point of the thermoplastic resin can be, for example, 150°C to 190°C or 160°C to 180°C for a resin with a relatively low melting point (such as a polyolefin-based resin), and 220°C to 350°C or 230°C to 320°C for a resin with a relatively high melting point (such as a polyamide-based resin).

[0127] In this disclosure, the melting point refers to the peak top temperature of the endothermic peak that appears when the temperature is increased from 23° C. at a rate of 10° C. / min using a differential scanning calorimeter (DSC), and when two or more endothermic peaks appear, it refers to the peak top temperature of the endothermic peak on the highest temperature side. Also, in this disclosure, the glass transition point is a temperature determined using a dynamic viscoelasticity measuring device as described above.

[0128] The polyolefin resin that is preferred as the polymer is a polymer obtained by polymerizing olefins (e.g., α-olefins) or alkenes as monomer units.Specific examples of the polyolefin resin include ethylene (co)polymers such as low-density polyethylene (e.g., linear low-density polyethylene), high-density polyethylene, ultra-low-density polyethylene, and ultra-high-molecular-weight polyethylene, polypropylene (co)polymers such as polypropylene, ethylene-propylene copolymer, and ethylene-propylene-diene copolymer, and copolymers of α-olefins such as ethylene, typified by ethylene-acrylic acid copolymer, ethylene-methyl methacrylate copolymer, and ethylene-glycidyl methacrylate copolymer.

[0129] The most preferred polyolefin resin here is polypropylene. In particular, polypropylene having a melt mass flow rate (MFR) of 3 g / 10 min or more and 30 g / 10 min or less, measured at 230 ° C. and a load of 21.2 N according to ISO1133, is preferred. The lower limit of MFR is more preferably 5 g / 10 min, even more preferably 6 g / 10 min, and most preferably 8 g / 10 min. The upper limit is more preferably 25 g / 10 min, even more preferably 20 g / 10 min, and most preferably 18 g / 10 min. It is desirable that MFR does not exceed the upper limit from the viewpoint of improving the toughness of the composition, and it is desirable that MFR does not fall below the lower limit from the viewpoint of the fluidity of the composition.

[0130] In addition, in order to increase the affinity with cellulose, an acid-modified polyolefin resin can also be suitably used. The acid in this case can be appropriately selected from polycarboxylic acids such as maleic acid, fumaric acid, succinic acid, phthalic acid, and their anhydrides, as well as citric acid. Among these, maleic acid or its anhydride is preferred because it is easy to increase the modification rate. There is no particular restriction on the modification method, but a method of heating to a melting point or higher in the presence or absence of a peroxide and melt-kneading is common. As the polyolefin resin to be acid-modified, all of the above-mentioned polyolefin resins can be used, but polypropylene is particularly suitable. Although the acid-modified polypropylene may be used alone, it is more preferable to use it in combination with unmodified polypropylene in order to adjust the modification rate of the resin as a whole. In this case, the ratio of the acid-modified polypropylene to all polypropylenes is 0.5% by mass to 50% by mass. A more preferable lower limit is 1% by mass, even more preferably 2% by mass, even more preferably 3% by mass, particularly preferably 4% by mass, and most preferably 5% by mass. A more preferred upper limit is 45% by mass, even more preferably 40% by mass, even more preferably 35% by mass, particularly preferably 30% by mass, and most preferably 20% by mass. In order to maintain the interfacial strength between the first component and the second component (in one embodiment, the interfacial strength between the resin and cellulose), the lower limit or more is preferred, and in order to maintain the ductility of the resin, the upper limit or less is preferred.

[0131] The melt mass flow rate (MFR) of the acid-modified polypropylene measured in accordance with ISO1133 at 230°C and a load of 21.2N is preferably 50g / 10min or more in order to enhance the affinity with the interface between the first component and the second component (for example, the interface between cellulose and resin). A more preferred lower limit is 100g / 10min, even more preferably 150g / 10min, and most preferably 200g / 10min. There is no particular upper limit, but it is 500g / 10min in order to maintain mechanical strength. By setting the MFR within this range, it is possible to enjoy the advantage that it is more likely to be present at the interface between the first component and the second component (the interface between cellulose and resin in one embodiment).

[0132] Examples of polyamide resins include polyamide 6, polyamide 11, and polyamide 12 obtained by polycondensation of lactams; diamines such as 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,7-heptanediamine, 2-methyl-1-6-hexanediamine, 1,8-octanediamine, 2-methyl-1,7-heptanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, and m-xylylenediamine; and butanedioic acid, pentanedioic acid, hexanedioic acid, heptanedioic acid, octanedioic acid, and nonanedioic acid. Polyamide 6,6, polyamide 6,10, polyamide 6,11, polyamide 6,12, polyamide 6,T, polyamide 6,I, polyamide 9,T, polyamide 10,T, polyamide 2M5,T, polyamide MXD,6, polyamide 6,C, polyamide 2M5,C, and copolymers obtained by copolymerizing these with dicarboxylic acids such as decanedioic acid, benzene-1,2-dicarboxylic acid, benzene-1,3-dicarboxylic acid, benzene-1,4-dicarboxylic acid, cyclohexane-1,3-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, and copolymers obtained by copolymerizing these with each other, such as copolymers of polyamide 6,T / 6,I, are exemplified.

[0133] Among these polyamide resins, aliphatic polyamides such as polyamide 6, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,11, and polyamide 6,12, and alicyclic polyamides such as polyamide 6,C and polyamide 2M5,C are more preferred.

[0134] The terminal carboxyl group concentration of the polyamide resin is not particularly limited, but may be preferably 20 μmol / g or more, or 25 μmol / g or more, and may be preferably 150 μmol / g or less, or 100 μmol / g or less.

[0135] The terminal amino group concentration of the polyamide resin may be preferably 20 μmol / g or more, or 30 μmol / g or more, and may be preferably 150 μmol / g or less, or 100 μmol / g or less.

[0136] The total concentration of terminal amino groups and terminal carboxyl groups in the polyamide resin is not particularly limited, but may be preferably 10 μmol / g or more, or 50 μmol / g or more, or 100 μmol / g or more, or 135 μmol / g or more, and from the viewpoint of preventing a decrease in viscosity due to the resin having an excessively low molecular weight and suppressing the occurrence of burrs and the like during molding, may be preferably 500 μmol / g or less, or 300 μmol / g or less, or 135 μmol / g or less, or 100 μmol / g or less.

[0137] The amino end group ratio ([NH2] / [COOH]) of the polyamide resin to the carboxyl end group is preferably more than 1.00, or 1.01 or more, or 1.05 or more, or 1.10 or more. There is no particular upper limit to the amino end group ratio, but from the viewpoint of maintaining a good color tone of the resin composition, it may be preferably 10,000 or less, 1,000 or less, 100 or less, or 10 or less.

[0138] The terminal group concentration of the polyamide resin can be adjusted by a known method, for example, by adding a terminal regulator that reacts with terminal groups, such as a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacid halide, a monoester, or a monoalcohol, to the polymerization solution so that the terminal group concentration is a predetermined value during polymerization of the polyamide.

[0139] The concentration of amino end groups and carboxyl end groups of the polyamide resin is 1 It can be determined from the integral value of the characteristic signal corresponding to each terminal group by H-NMR. Specifically, the method described in JP-A-7-228775 is recommended.

[0140] The polyamide resin preferably has an intrinsic viscosity [η] of 0.6 to 2.0 dL / g, more preferably 0.7 to 1.4 dL / g, further preferably 0.7 to 1.2 dL / g, and particularly preferably 0.7 to 1.0 dL / g, measured in concentrated sulfuric acid at 30° C. Use of a polyamide having an intrinsic viscosity within the above range provides the advantage of increasing the flowability of the resin composition in the mold during injection molding and improving the appearance of the molded piece.

[0141] In the present disclosure, the term "intrinsic viscosity" is synonymous with the viscosity generally called limiting viscosity, and can be measured, for example, by the method described in Polymer Process Engineering (Prentice-Hall, Inc. 1994), pages 291 to 294.

[0142] The polyester resin may be one or more selected from polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoic acid (PHA), polylactic acid (PLA), polyarylate (PAR), polycarbonate (PC), etc. More preferred examples of the polyester resin include PET, PBS, PBSA, PBT, and PEN, and even more preferred examples include PBS, PBSA, and PBT.

[0143] In addition, the polyester resin can freely change the terminal group depending on the monomer ratio during polymerization and the presence or absence and amount of addition of a terminal stabilizer, but the carboxyl terminal group ratio ([COOH] / [total terminal groups]) to the total terminal groups of the polyester resin is more preferably 0.30 to 0.95. The lower limit of the carboxyl terminal group ratio is more preferably 0.35, even more preferably 0.40, and most preferably 0.45. The upper limit of the carboxyl terminal group ratio is more preferably 0.90, even more preferably 0.85, and most preferably 0.80. The carboxyl terminal group ratio is preferably 0.30 or more from the viewpoint of dispersibility of cellulose in the composition, and is preferably 0.95 or less from the viewpoint of the color tone of the obtained composition.

[0144] As polyacetal resins, homopolyacetals made from formaldehyde and copolyacetals containing trioxane as a main monomer and 1,3-dioxolane as a comonomer component are common. Both can be used, but copolyacetals are preferred from the viewpoint of thermal stability during processing. In particular, the amount of the structure derived from the comonomer component (e.g., 1,3-dioxolane) is more preferably within the range of 0.01 to 4 mol%. The preferred lower limit of the amount of the structure derived from the comonomer component is 0.05 mol%, more preferably 0.1 mol%, and even more preferably 0.2 mol%. The preferred upper limit is 3.5 mol%, more preferably 3.0 mol%, even more preferably 2.5 mol%, and most preferably 2.3 mol%.

[0145] From the viewpoint of thermal stability during extrusion and molding, the lower limit is desirably within the above-mentioned range, and from the viewpoint of mechanical strength, the upper limit is desirably within the above-mentioned range.

[0146] As the polymer, from the viewpoint of affinity with cellulose, for example, a polymer having a hydrophilic group (for example, one or more selected from a hydroxyl group, an amino group, and a carboxyl group) is particularly preferred. Suitable examples of the polymer having a hydrophilic group are one or more selected from the group consisting of acid-modified polyolefin resins, polyacetal resins, polycarbonate resins, polyamide resins, polyester resins, polyphenylene ether resins, and acrylic resins. Among them, polyamide resins and maleated polypropylene are preferred.

[0147] <Second Ingredient> The second component is an organic fiber and / or a polymer. In one embodiment, the second component is dispersed in the first component by being mixed with the first component, and the physical properties of the resin composition (in one embodiment, one or more selected from the group consisting of tensile elongation, flexural modulus, thermal expansion coefficient, and physical property stability, preferably all of these) can be improved compared to when the second component is not present. In the resin composition, the amount of the second component relative to 100 mass% of the entire resin composition, or the amount of the second component relative to 100 mass% of the total of the first component and the second component, is preferably 0.1 mass% or more, or 0.5 mass% or more, or 1 mass% or more, or 3 mass% or more, and preferably 30 mass% or less, or 25 mass% or less, or 20 mass% or less, or 15 mass% or less. When the amount of the second component is in the above range, it is preferable from the viewpoint of high tensile elongation, high flexural modulus, low thermal expansion coefficient, and / or good physical property stability. Preferred examples of the organic fibers and polymers will be described below.

[0148] <Organic fiber> The organic fiber is a fiber composed of an organic material. In one embodiment, the organic fiber is a polymer fiber, in one embodiment, a fiber having a hydrogen bond-forming structure (e.g., OH structure and / or NH structure), and in one embodiment, one or more selected from the group consisting of natural fibers (e.g., cellulose fibers, cellulose nanocrystals, chitin fibers, chitosan fibers, wool, etc.) and synthetic fibers (e.g., aramid fibers, nylon fibers, acrylic fibers, polyester fibers, vinylon fibers, rayon fibers, polyurethane fibers, etc.). In the present disclosure, cellulose fibers refer to cellulose having an L / D of 30 or more, and cellulose nanocrystals refer to cellulose having an average fiber diameter of 1000 nm or less and an L / D of less than 30. Organic fibers having a hydrogen bond-forming structure tend to be inherently easily aggregated by hydrogen bonds, but according to the method of the present disclosure, even such organic fibers can be well finely dispersed in the first component.

[0149] In the resin composition, the amount of organic fibers relative to 100% by mass of the entire resin composition is preferably 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, and preferably 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. The amount of organic fibers in the above range is preferable from the viewpoints of high tensile elongation, high flexural modulus, low thermal expansion coefficient, and / or good physical property stability.

[0150] [Cellulose fiber] In one embodiment, the organic fiber includes or is a cellulose fiber. The raw material of the cellulose fiber includes natural cellulose fiber and regenerated cellulose fiber. As the natural cellulose fiber, wood pulp obtained from wood species (broadleaf or coniferous), non-wood pulp obtained from non-wood species (bamboo, hemp-based fiber, bagasse, kenaf, linter, etc.), and refined pulp thereof (refined linter, etc.) can be used. As the non-wood pulp, cotton-derived pulp including cotton linter pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, straw-derived pulp, etc. can be used. Cotton-derived pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, and straw-derived pulp each include cellulose fibers made from purified pulp obtained from raw materials such as cotton lint, cotton linter, hemp-based abaca (e.g., from Ecuador or the Philippines), zaisal, bagasse, kenaf, bamboo, straw, etc., through a refining process such as delignification by cooking treatment, a bleaching process, etc.

[0151] In one embodiment, the cellulose fiber is a cellulose nanofiber, which can be obtained, for example, by treating the above-mentioned pulp with hot water of 100° C. or higher to hydrolyze and weaken the hemicellulose portion, and then defibrating the pulp by a pulverization method using a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, or the like.

[0152] In one aspect, the number average fiber diameter of the cellulose nanofibers is 2 to 1000 nm, and is preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, or 50 nm or more, or 100 nm or more, and preferably 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less, or 200 nm or less.

[0153] The number average fiber length / number average fiber diameter ratio (L / D) of the cellulose nanofibers may, in one embodiment, be 30 or more, or 50 or more, or 80 or more, or 100 or more, and in one embodiment, may be 5,000 or less, or 4,000 or less, or 3,000 or less.

[0154] In one embodiment, the number average fiber diameter (D), number average fiber length (L), and L / D ratio of the cellulose fibers of the present disclosure are values ​​measured by the following procedure using a scanning electron microscope (SEM). An aqueous dispersion of cellulose fibers is replaced with tert-butanol, diluted to 0.001 to 0.1 mass%, and dispersed using a high-shear homogenizer (e.g., IKA, product name "Ultra Turrax T18") under processing conditions: rotation speed 15,000 rpm x 3 minutes, cast on an osmium-deposited silicon substrate, and air-dried to obtain a measurement sample, which is measured using a high-resolution scanning electron microscope (SEM). Specifically, the length (L) and diameter (D) of 100 randomly selected fibrous substances are measured in an observation field where the magnification is adjusted so that at least 100 fibrous substances are observed, and the ratio (L / D) is calculated. The number average value of the length (L), the number average value of the diameter (D), and the number average value of the ratio (L / D) of the cellulose fibers are calculated.

[0155] The length, diameter, and L / D ratio of the cellulose fibers in the resin composition and in the molded product can be measured by the above-mentioned method using a 0.001 to 0.1 mass% dispersion prepared by dissolving the polymer component in an organic or inorganic solvent capable of dissolving the polymer component, separating the cellulose fibers, thoroughly washing the cellulose fibers with the solvent, and then replacing the dispersion with tert-butanol, and redispersing the dispersion using a high-shear homogenizer (for example, IKA product, trade name "Ultra-Turrax T18").

[0156] From the viewpoint of obtaining a resin composition having excellent heat resistance, mechanical strength and dimensional stability, the crystallinity of the cellulose fiber is preferably 55% or more, or 60% or more, or 70% or more, or 80% or more. When the crystallinity is within this range, the mechanical properties (heat resistance, strength, dimensional stability) of the cellulose fiber itself are high, so that when the cellulose fiber is dispersed in a polymer, the heat resistance, strength, and dimensional stability of the resin composition tend to be high. Although a high crystallinity is preferable, the upper limit from the viewpoint of production is preferably 99%.

[0157] The degree of crystallinity here, when the cellulose fiber is cellulose type I crystal (derived from natural cellulose), is calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring the sample by wide-angle X-ray diffraction, using the Segal method and the following formula. Crystallinity (%) = ([diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [diffraction intensity due to amorphous matter at 2θ / deg. = 18]) / [diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100

[0158] When the cellulose fiber is a cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%) =h1 / h0 ×100

[0159] Known crystalline forms of cellulose include type I, type II, type III, and type IV, among which types I and II are particularly widely used, and types III and IV are obtained on a laboratory scale but are not widely used on an industrial scale. The cellulose fibers of the present disclosure are preferably cellulose fibers containing cellulose type I crystals or cellulose type II crystals, since they have relatively high structural mobility and, by dispersing the cellulose fibers in a resin, a resin composition having a lower linear expansion coefficient and superior strength and elongation during tensile and bending deformation can be obtained, and more preferably cellulose fibers containing cellulose type I crystals and having a crystallinity of 55% or more.

[0160] In addition, the degree of polymerization of the cellulose fibers is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, and preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, and more preferably 3000 or less.

[0161] From the viewpoint of processability and mechanical property expression, it is desirable that the polymerization degree of the cellulose fiber is within the above-mentioned range. From the viewpoint of processability, it is preferable that the polymerization degree is not too high, and from the viewpoint of mechanical property expression, it is desirable that the polymerization degree is not too low.

[0162] The degree of polymerization of cellulose fibers means the average degree of polymerization measured according to the reduced specific viscosity method using a copper ethylenediamine solution described in the Verification Test (3) of the "15th Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)."

[0163] In one embodiment, the weight average molecular weight (Mw) of the cellulose fiber is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecule are the starting points of thermal decomposition, when the weight average molecular weight of the cellulose molecule is not only large but also has a narrow molecular weight distribution width, a particularly high heat resistant cellulose fiber and a resin composition containing the cellulose fiber and a resin can be obtained. The weight average molecular weight (Mw) of the cellulose fiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of the cellulose raw material. From the viewpoint of ease of production of cellulose fibers, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more. Mw can be controlled within the above range by selecting a cellulose raw material having an Mw appropriate for the purpose, performing a physical treatment and / or a chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. Mw / Mn can also be controlled within the above range by selecting a cellulose raw material having an Mw / Mn appropriate for the purpose, performing a physical treatment and / or a chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include dry or wet grinding using a microfluidizer, ball mill, disk mill, etc., physical treatment that applies mechanical forces such as impact, shear, shear, and friction using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, etc., and examples of the chemical treatment include digestion, bleaching, acid treatment, and regenerated cellulose.

[0164] The weight average molecular weight and number average molecular weight of the cellulose fiber referred to here are values ​​obtained by dissolving the cellulose fiber in N,N-dimethylacetamide containing added lithium chloride and then performing gel permeation chromatography using N,N-dimethylacetamide as a solvent.

[0165] Methods for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose fibers include hydrolysis. The hydrolysis promotes depolymerization of amorphous cellulose inside the cellulose, decreasing the average degree of polymerization. At the same time, the hydrolysis removes impurities such as hemicellulose and lignin in addition to the amorphous cellulose described above, making the inside of the fiber porous. This makes the cellulose more susceptible to mechanical treatment in a process of applying mechanical shear force to the cellulose, such as during the kneading process described below, and makes the cellulose more easily pulverized.

[0166] Alkali-soluble polysaccharides that may be contained in cellulose fibers include hemicellulose, β-cellulose, and γ-cellulose. Alkali-soluble polysaccharides are understood by those skilled in the art as components obtained as the alkali-soluble portion of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components obtained by removing α-cellulose from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups and have poor heat resistance, and may cause inconveniences such as decomposition when exposed to heat, yellowing during heat aging, and a decrease in the strength of cellulose fibers. Therefore, it is preferable that the content of alkali-soluble polysaccharides in cellulose fibers is low.

[0167] In one embodiment, the average content of alkali-soluble polysaccharides in the cellulose fibers is preferably 20% by mass or less, or 18% by mass or less, or 15% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of obtaining good dispersibility of the cellulose fibers. The above content may be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 6% by mass or more, from the viewpoint of ease of production of the cellulose fibers. In one embodiment, the average content of alkali-soluble polysaccharides in the cellulose raw material may be 13% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less, and is most preferably 0% by mass, but may be, for example, 3% by mass or more, or 6% by mass or more, from the viewpoint of ease of availability of the cellulose raw material.

[0168] The average alkali-soluble polysaccharide content can be determined by the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000), by subtracting the α-cellulose content from the holocellulose content (Wise method). This method is understood in the industry as a method for measuring the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents is taken as the average alkali-soluble polysaccharide content.

[0169] In one embodiment, the average content of acid-insoluble components in the cellulose fibers is preferably 10% by mass or less, 5% by mass or less, or 3% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of avoiding a decrease in heat resistance of the cellulose fibers and the associated discoloration. From the viewpoint of ease of production of the cellulose fibers, the content may be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.

[0170] The average acid-insoluble content is determined as a quantitative determination of the acid-insoluble content using the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000). This method is understood in the industry as a method for measuring the amount of lignin. The sample is stirred in a sulfuric acid solution to dissolve cellulose, hemicellulose, etc., and then filtered through a glass fiber filter paper, and the resulting residue corresponds to the acid-insoluble content. The acid-insoluble content is calculated from the weight of the acid-insoluble content, and the number average of the acid-insoluble content calculated for the three samples is taken as the average acid-insoluble content.

[0171] The cellulose fibers may be chemically treated (e.g., oxidized or chemically modified with a modifying agent). As an example, finely divided cellulose fibers obtained by oxidizing cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical as shown in Cellulose (1998) 5, 153-164, followed by washing and mechanical fiberization, may be used.

[0172] [Hydrophobicity of cellulose fibers] The cellulose fibers may be cellulose fibers hydrophobized by a hydrophobizing agent (also referred to as chemically modified cellulose fibers in the present disclosure). Hydrophobization weakens hydrogen bonds between cellulose fibers, contributing to fine dispersion, and improves heat resistance as cellulose fibers, making it possible to suppress deterioration due to kneading with resin, and has the effect of making cellulose fibers less likely to become the starting point of physical property defects. As the hydrophobizing agent (also referred to as a modifying agent in the present disclosure), a compound that reacts with the hydroxyl group of cellulose can be used, and examples of the hydrophobizing agent include an esterifying agent, an etherifying agent, and a silylating agent. In particular, an esterifying agent is preferred. In a preferred embodiment, the hydrophobization is acylation using an esterifying agent. As the esterifying agent, acid halides, acid anhydrides, and carboxylic acid vinyl esters are preferred. In a particularly preferred embodiment, the hydrophobization is acetylation. Among these esterification reactants, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate, and acetic acid, and among these, acetic anhydride and vinyl acetate are preferred from the viewpoint of reaction efficiency.

[0173] When obtaining hydrophobized cellulose nanofibers, there is no particular limitation on the method for pulverizing natural cellulose raw materials to reduce the fiber diameter, but it is preferable to make the defibration processing conditions (method of applying a shear field, magnitude of the shear field, etc.) more efficient. In particular, by impregnating a cellulose raw material having a cellulose purity of 85% by mass or more with a defibration solution containing an aprotic solvent, cellulose swelling occurs in a short time, and the cellulose is pulverized by only applying slight stirring and shear energy. Then, hydrophobized cellulose nanofibers can be obtained by adding a cellulose modifying agent immediately after defibration. This method is preferable from the viewpoints of production efficiency and purification efficiency (i.e., high cellulose purity of hydrophobized cellulose nanofibers) and physical properties of the resin composition.

[0174] Aprotic solvents include, for example, alkyl sulfoxides, alkyl amides, pyrrolidones, etc., which can be used alone or in combination of two or more. Among these aprotic solvents, DMSO (29.8), DMF (26.6), DMAc (27.8), NMP (27.3) (numbers in parentheses are donor numbers), etc., and especially DMSO can be used to more efficiently produce hydrophobic cellulose nanofibers with a high thermal decomposition onset temperature. The mechanism of this action is not necessarily clear, but it is presumed to be due to uniform micro-swelling of the fiber raw material in the aprotic solvent.

[0175] The degree of hydrophobicity (degree of modification) of cellulose fibers is expressed as the average degree of substitution of hydroxyl groups (also referred to as DS, the average number of hydroxyl groups substituted per glucose, which is the basic structural unit of cellulose). In one embodiment, the DS of the chemically modified cellulose fibers is preferably 0.01 or more and 2.0 or less. If the DS is 0.01 or more, a resin composition containing chemically modified cellulose fibers having a high thermal decomposition onset temperature can be obtained. On the other hand, if the DS is 2.0 or less, an unmodified cellulose skeleton remains in the chemically modified cellulose fibers, so that a resin composition containing chemically modified cellulose fibers having both high tensile strength and dimensional stability derived from cellulose fibers and a high thermal decomposition onset temperature derived from chemical modification can be obtained. The DS is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.2 or more, and most preferably 0.3 or more, and more preferably 1.8 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less.

[0176] In the reflection infrared absorption spectrum of hydrophobized cellulose fibers, the peak position of the absorption band changes depending on the type of hydrophobic modification group. From the change in peak position, it is possible to determine which absorption band the peak is based on, and to identify the modification group. In addition, the modification rate can be calculated from the peak intensity ratio between the peak derived from the modification group and the peak derived from the cellulose skeleton.

[0177] When the modifying group is an acyl group, the degree of acyl substitution (DS) can be calculated from the reflection infrared absorption spectrum of the esterified cellulose fiber. The peak of the absorption band of C=O based on the acyl group is 1730 cm -1 The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose is calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurement of esterified cellulose and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on the acyl group to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using

[0178] In addition, when it is difficult to perform appropriate measurement using the reflection infrared absorption spectrum, the chromaticity can be calculated using the following formula using solid-state NMR, based on the total area intensity (Inp) of the signals assigned to carbons C1-C6 derived from the pyranose ring of cellulose, which appear in the range of 50 ppm to 110 ppm, relative to the area intensity (Inf) of the signal assigned to one carbon atom derived from the modifying group. DS = (Inf) x 6 / (Inp) For example, when the modifying group is an acetyl group, the signal at 23 ppm assigned to -CH3 may be used.

[0179] [Cellulose nanocrystals] The cellulose nanocrystal may be crystalline cellulose that remains after cutting pulp or the like, and dissolving the amorphous part of the cellulose in an acid such as hydrochloric acid or sulfuric acid. In one embodiment, the length / diameter ratio (L / D ratio) of the cellulose nanocrystal is less than 30. In one embodiment, the average diameter of the cellulose nanocrystal is 1000 nm or less, preferably 500 nm or less, or 200 nm or less, and preferably 10 nm or more, 20 nm or more, or 30 nm or more. The L / D ratio and average diameter are values ​​measured by the same method as the average fiber diameter of cellulose fibers.

[0180] The L / D of the cellulose nanocrystals is less than 30 in one embodiment, and preferably 25 or less, or 20 or less, or 15 or less, or 10 or less, or 5 or less. The lower limit is not particularly limited, but may be greater than 1. The cellulose nanocrystals can improve the tensile elongation of the resin composition. In one embodiment, the cellulose whiskers may have the same properties (e.g., unmodified or modified) as those described above for the cellulose fibers, except for their size.

[0181] [Chitin fiber, chitosan fiber] The chitin fiber may be a fiber mainly composed of acetylglucosamine polymer, i.e., chitin, obtained by separating and purifying the raw material, such as the shell of crustaceans. The chitosan fiber may be a fiber mainly composed of glucosamine polymer, i.e., chitosan, obtained by deacetylating chitin fiber. The average diameter of the chitin fiber and the chitosan fiber is, in one embodiment, 2 to 1000 nm, preferably 500 nm or less or 200 nm or less, and preferably 10 nm or more, 20 nm or more, or 30 nm or more. The L / D of chitin fibers and chitosan fibers, respectively, in one embodiment is 30 or more, preferably 50 or more, or 100 or more, and in one embodiment, may be 100,000 or less, or 50,000 or less, or 10,000 or less, or 5,000 or less.

[0182] [Aramid fiber] Aramid fibers are synthetic fibers mainly composed of aromatic polyamide, and are roughly classified into para-aramid fibers and meta-aramid fibers according to the aromatic structure. The average diameter of the aramid fibers is 2 to 1000 nm in one aspect, preferably 500 nm or less or 200 nm or less, and preferably 10 nm or more, 20 nm or more, or 30 nm or more. The L / D of the aramid fibers may be 30 or more in one embodiment, preferably 50 or more, or 100 or more, and in one embodiment, 100,000 or less, or 50,000 or less, or 10,000 or less, or 5,000 or less.

[0183] The fiber length, fiber diameter and L / D of organic fibers other than cellulose fibers are measured in the same manner as for cellulose fibers.

[0184] <Polymer> In one embodiment, the second component includes a polymer. In one embodiment, the polymer in the first component and the polymer in the second component are different from each other in the molecular structure and / or molecular weight of at least one polymer constituting them. The polymer as the second component may include, for example, one or more selected from the group consisting of polyolefin-based resins, polyamide-based resins, polyester-based resins, polyacetal-based resins, polyphenylene sulfide-based resins, polyvinyl alcohol-based resins, polyvinylidene chloride-based resins, polystyrene-based resins, polyvinyl chloride-based resins, polycarbonate-based resins, polymethyl methacrylate-based resins, polyurethane-based resins, fluorine-based resins, polyacrylonitrile-based resins, polybutene-based resins, polyimide-based resins, polyarylate-based resins, cellulose-based resins, polyphenylene ether-based resins, elastomers, and modified products thereof (e.g., modified products of maleic anhydride, etc.), or may be one or more selected from the group consisting of these.

[0185] [Polyphenylene ether] Polyphenylene ether is represented by the following general formula (1): [ka] (In formula (1), R 1 , R 2 , R 3 , and R 4are each independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halohydrocarbyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and n is an integer of 20 or more. The polyphenylene ether has a structure represented by the following formula: The use of polyphenylene ether as the second component is advantageous in terms of the bending properties of the resin composition.

[0186] In the above formula (1), R 1 , R 2 , R 3 , and R 4 Examples of the halogen atom represented by the formula (I) include a fluorine atom, a chlorine atom, a bromine atom, etc., and a chlorine atom and a bromine atom are preferred.

[0187] In the above formula (1), R 1 , R 2 , R 3 , and R 4 The "alkyl group" represented by the formula (I) represents a linear or branched alkyl group having preferably 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and examples thereof include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, etc. Methyl and ethyl are preferred, and methyl is more preferred.

[0188] In the above formula (1), R 1 , R 2 , R 3 , and R 4The alkyl group represented by the formula (I) may be substituted with one or more substituents at substitutable positions. Examples of such substituents include halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms), alkyl groups having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl), aryl groups (e.g., phenyl, naphthyl), alkenyl groups (e.g., ethenyl, 1-propenyl, 2-propenyl), alkynyl groups (e.g., ethynyl, 1-propynyl, 2-propynyl), aralkyl groups (e.g., benzyl, phenethyl), alkoxy groups (e.g., methoxy, ethoxy), and the like.

[0189] In the above formula (1), n ​​may be 20 or more, or 100 or more, or 200 or more, and may be 2000 or less, or 1000 or less, or 400 or less.

[0190] The polyphenylene ether is not particularly limited, and known ones may be used. For example, poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), etc. may be mentioned, and further, polyphenylene ether copolymers such as 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol or 2-methyl-6-butylphenol) may also be used. Among the above, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is more preferred. These polyphenylene ethers may be used alone or in combination of two or more kinds.

[0191] The intrinsic viscosity [η] of the polyphenylene ether is preferably 0.1 dl / g or more, or 0.2 dl / g or more, or 0.3 dl / g or more from the viewpoint of obtaining a resin composition with high rigidity, and is preferably 1.0 dl / g or less, or 0.7 dl / g or less, or 0.6 dl / g or less, or 0.5 dl / g or less from the viewpoint of imparting good fluidity to the resin composition. The intrinsic viscosity is a value measured in chloroform at 25°C.

[0192] In one embodiment, the polyphenylene ether may be at least partially acid-modified by reacting the polyphenylene ether with a modifier (e.g., α,β-unsaturated carboxylic acid and its derivatives).

[0193] Examples of α,β-unsaturated carboxylic acids include monobasic acids such as (meth)acrylic acid, crotonic acid, isocrotonic acid, furan acid, pentenoic acid, vinylacetic acid, and angelic acid; dibasic acids such as maleic acid, chloromaleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, and endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (nadic acid); and tribasic acids such as citric acid and aconitic acid.

[0194] Examples of the derivatives of α,β-unsaturated carboxylic acids include acid halides, amides, imides, acid anhydrides, and esters of the above-mentioned α,β-unsaturated carboxylic acids. For example, malenyl chloride, acrylamide, maleimide, N-phenylmaleimide, N-methylmaleimide, N-ethylmaleimide, maleic anhydride, itaconic anhydride, glutaconic anhydride, citraconic anhydride, nadic anhydride, aconic anhydride, methyl (meth)acrylate, monomethyl maleate, dimethyl maleate, diethyl itaconate, dibutyl citraconate, glycidyl (meth)acrylate, and diglycidyl maleate. Among these, examples of preferred modifiers include maleic acid, citric acid, itaconic acid, itaconic anhydride, and maleic anhydride, and more preferably, citric acid and maleic anhydride.

[0195] The degree of acid modification of the polyphenylene ether is preferably 0.01% or more, or 0.1% or more, or 0.2% or more, or 0.25% or more from the viewpoint of favorably finely dispersing the second component, and is preferably 10% or less, or 5% or less, or 2% or less, or 1% or less, or 0.7% or less, or 0.6% or less from the viewpoint of favorably obtaining the advantages of using the polyphenylene ether. The polyphenylene ether of the present disclosure may be a mixture of two or more polymers having different acid modification degrees. In this case, it is preferable that the degree of acid modification of the entire polyphenylene ether in the resin composition is in the above range. The degree of acid modification is an addition rate calculated from infrared spectroscopy measurement. When the acidic functional group is derived from maleic anhydride, a mixture of polyphenylene ether and maleic anhydride is used to obtain the 1790 cm -1 After preparing a calibration curve for the peak at 1790 cm for maleic anhydride-modified polyphenylene ether, -1 The addition rate is calculated from the peak intensity.

[0196] Examples of the method for modifying polyphenylene ether with an acid include a method of reacting a modifier with polyphenylene ether in a fluid state (for example, by melting, or dispersing or dissolving in a solvent), a method of reacting a modifier with powdered polyphenylene ether in the presence of a modifier at a temperature below the glass transition point of polyphenylene ether, etc. Examples of the method for reacting a modifier with polyphenylene ether in a fluid state include a method of melt-kneading polyphenylene ether and a modifier at 250°C to 350°C for 5 seconds to 30 minutes using a roll mill, Banbury mixer, extruder, etc., and a method of dissolving polyphenylene ether in an organic solvent (for example, toluene, xylene, decalin, tetralin, etc.), adding a modifier, and heating. An example of a method for reacting a modifier with powdered polyphenylene ether is a method in which predetermined amounts of polyphenylene ether and modifier are charged into a stirring device capable of high-speed stirring, and the temperature of the contents is maintained at 160°C to 200°C for at least 30 seconds or more by the shear heat generated by high-speed stirring and / or heat transfer from the jacket.

[0197] The reaction may be carried out in the presence of a radical initiator. Examples of the radical initiator include organic peroxides (benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, cumene hydroperoxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, etc.) and azo compounds (azobisisobutylnitrile, dimethylazoisobutyrate, etc.). The amount of the radical initiator used may be, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of polyphenylene ether.

[0198] In one embodiment, the polyphenylene ether may be a mixture of polyphenylene ether having an acidic functional group and polyphenylene ether not having an acidic functional group. The mixing ratio of the polyphenylene ether having an acidic functional group and the polyphenylene ether not having an acidic functional group, when the total of both is 100 mass%, is preferably 10 mass% or more, more preferably 20 mass% or more, even more preferably 30 mass% or more, and most preferably 40 mass% or more, from the viewpoint of obtaining the advantages of the polyphenylene ether having an acidic functional group. The upper limit is not particularly limited, and substantially all of the polyphenylene ether may be polyphenylene ether having an acidic functional group, but from the viewpoint of not causing problems in flowability during melting, it is desirable to be 80 mass% or less.

[0199] The polymer as the second component is an elastomer in one embodiment. In the present disclosure, an elastomer is a material (specifically, a natural or synthetic polymer material) that is elastic at room temperature (23°C). Elastomers are advantageous in terms of improving the toughness and elongation (especially elongation in a low temperature environment) of the resin composition.

[0200] Specific examples of elastomers include natural rubber, conjugated diene compound polymers, aromatic compound-conjugated diene copolymers, hydrogenated aromatic compound-conjugated diene copolymers, polyolefins, polyester-based elastomers, polyurethane-based elastomers, polyamide-based elastomers, and elastomers having a core-shell structure. Among these, from the viewpoint of ease of modification reaction of acidic functional groups described below, aromatic compound-conjugated diene copolymers and hydrogenated products thereof, polyolefins, and elastomers having a core-shell structure are preferred. As the aromatic compound-conjugated diene copolymers and hydrogenated products thereof, aromatic compound-conjugated diene block copolymers and hydrogenated products thereof are more preferred, and as the polyolefins, copolymers of ethylene and α-olefins are more preferred.

[0201] In one embodiment, the elastomer is at least one selected from the group consisting of an ethylene-α-olefin copolymer, a block copolymer of an aromatic vinyl compound and a conjugated diene compound, and a hydrogenated product of a block copolymer of an aromatic vinyl compound and a conjugated diene compound.

[0202] In the present disclosure, the aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block (A) mainly made of an aromatic vinyl compound and a polymer block (B) mainly made of a conjugated diene compound. From the viewpoint of impact strength expression, a block copolymer in which the bonding type of each block is AB type, ABA type, or ABAB type is preferable, and an ABA type or ABAB type is more preferable.

[0203] The mass ratio of the aromatic vinyl compound unit to the conjugated diene compound unit in the block copolymer is preferably 10 / 90 to 70 / 30. More preferably, it is 15 / 85 to 55 / 45, and most preferably 20 / 80 to 45 / 55. Furthermore, these may be blended with two or more different mass ratios of the aromatic vinyl compound to the conjugated diene compound. Specific examples of the aromatic vinyl compound include styrene, α-methylstyrene, vinyltoluene, etc., and one or more compounds selected from these are used, among which styrene is particularly preferred.

[0204] Specific examples of the conjugated diene compound include butadiene, isoprene, piperylene, 1,3-pentadiene, etc., and one or more compounds selected from these are used, but among these, butadiene, isoprene, and combinations thereof are preferred, and butadiene is particularly preferred. When butadiene is used as the conjugated diene compound of the block copolymer, the microstructure of the polybutadiene block portion preferably has a 1,2-vinyl content or a total amount of the 1,2-vinyl content and the 3,4-vinyl content of 5 to 80% on a molar basis, more preferably 10 to 50%, and most preferably 15 to 40%, from the viewpoint of suppressing crystallization of the soft segment.

[0205] The aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block mainly made of an aromatic vinyl compound and a polymer block mainly made of a conjugated diene compound, and is a block copolymer that has not been subjected to a hydrogenation treatment. The hydrogenated product of the block copolymer of an aromatic vinyl compound and a conjugated diene compound refers to a block copolymer of an aromatic vinyl compound and a conjugated diene compound, which is hydrogenated to control the aliphatic double bonds of the polymer block mainly made of a diene compound in the range of more than 0% to 100%. From the viewpoint of suppressing thermal deterioration during processing, the hydrogenation rate of the hydrogenated product of the block copolymer is preferably 50% or more, more preferably 80% or more, and most preferably 98% or more, and from the viewpoint of low temperature toughness, it is preferably 50% or less, more preferably 20% or less, and most preferably 0% (i.e., a block copolymer of an aromatic vinyl compound and a conjugated diene compound).

[0206] In addition, the molecular weight of each of the block copolymer of an aromatic vinyl compound and a conjugated diene compound and its hydrogenated product is preferably a number average molecular weight (Mn) of 10,000 to 500,000, and most preferably 40,000 to 250,000, from the viewpoint of achieving both impact strength and fluidity. In the present disclosure, the number average molecular weight is a value measured using a gel permeation chromatography device, chloroform as a solvent, at a measurement temperature of 40°C, and converted into polystyrene standard, unless otherwise specified.

[0207] These aromatic vinyl compound-conjugated diene compound block copolymers may be used in a mixture of two or more types of copolymers having different bond types, different molecular weights, different aromatic vinyl compound types, different conjugated diene compound types, different 1,2-vinyl contents or the total amount of 1,2-vinyl content and 3,4-vinyl content, different aromatic vinyl compound component contents, different hydrogenation rates, etc. In a mixture of copolymers having different hydrogenation rates, the preferred hydrogenation rate of the mixture is as described above.

[0208] As the polyolefin, from the viewpoint of impact resistance, an ethylene-α-olefin copolymer can be suitably used. Examples of monomers that can be copolymerized with ethylene units include aliphatic substituted vinyl monomers such as propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, heptene-1, octene-1, nonene-1, decene-1, undecene-1, dodecene-1, tridecene-1, tetradecene-1, pentadecene-1, hexadecene-1, heptadecene-1, octadecene-1, nonadecene-1, or eicosene-1, isobutylene, and aromatic vinyl monomers such as styrene and substituted styrene, ester vinyl monomers such as vinyl acetate, acrylic acid esters, methacrylic acid esters, glycidyl acrylic acid esters, glycidyl methacrylic acid esters, and hydroxyethyl methacrylic acid esters, acrylamide, allylamine, vinyl-p-aminobenzene, and nitrogen-containing vinyl monomers such as acrylonitrile, and dienes such as butadiene, cyclopentadiene, 1,4-hexadiene, and isoprene.

[0209] Preferably, it is a copolymer of ethylene and one or more α-olefins having 3 to 20 carbon atoms, more preferably a copolymer of ethylene and one or more α-olefins having 3 to 16 carbon atoms, and most preferably a copolymer of ethylene and one or more α-olefins having 3 to 12 carbon atoms. From the viewpoint of impact resistance, the molecular weight of the ethylene-α-olefin copolymer is preferably 10,000 or more, more preferably 10,000 to 100,000, and even more preferably 20,000 to 60,000, as measured by a gel permeation chromatography measuring device using 1,2,4-trichlorobenzene as a solvent at 140°C and using polystyrene standards. From the viewpoint of impact resistance, the molecular weight distribution (weight average molecular weight / number average molecular weight: Mw / Mn) is preferably 3 or less, and even more preferably 1.8 to 2.7.

[0210] Moreover, the preferred content of ethylene units in the ethylene-α-olefin copolymer is 30 to 95% by mass based on the total amount of the ethylene-α-olefin copolymer, from the viewpoint of ease of handling during processing.

[0211] These preferred ethylene-α-olefin copolymers can be produced, for example, by the production methods described in JP-B-4-12283, JP-A-60-35006, JP-A-60-35007, JP-A-60-35008, JP-A-5-155930, JP-A-3-163088, and U.S. Pat. No. 5,272,236.

[0212] In the present disclosure, the elastomer having a core-shell structure includes a core-shell type elastomer having a core that is a particulate rubber and a shell that is a glassy graft layer formed on the outside of the core. As the rubber component as the core, butadiene rubber, acrylic rubber, silicone-acrylic composite rubber, etc. can be suitably used. As the shell, a glassy polymer such as styrene resin, acrylonitrile-styrene copolymer, acrylic resin, etc. is suitable. For example, when the first component contains polyamide, an elastomer having a core-shell structure having a butadiene rubber core and an acrylic resin shell can be suitably used from the viewpoint of compatibility with polyamide.

[0213] In one embodiment, at least a part of the elastomer has an acidic functional group. In this disclosure, the term "an elastomer has an acidic functional group" means that the acidic functional group is added to the molecular skeleton of the elastomer via a chemical bond. In this disclosure, the term "acidic functional group" means a functional group capable of reacting with a basic functional group, and specific examples thereof include a hydroxyl group, a carboxyl group, a carboxylate group, a sulfo group, and an acid anhydride group.

[0214] From the viewpoint of compatibility with a second polymer having an acidic functional group or a polyphenylene ether having an acidic functional group, the amount of acidic functional groups added in the elastomer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less, based on 100% by mass of the elastomer. The number of acidic functional groups is a value obtained by measuring a calibration curve sample in which an acidic substance is mixed in advance with an infrared absorption spectrometer, and measuring the sample based on a calibration curve prepared using the characteristic absorption band of the acid.

[0215] Examples of elastomers having an acidic functional group include elastomers having a core-shell structure having a shell layer formed using acrylic acid or the like as a copolymerization component, and elastomers which are modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof to an ethylene-α-olefin copolymer, polyolefin, aromatic compound-conjugated diene copolymer, or a hydrogenated aromatic compound-conjugated diene copolymer containing acrylic acid or the like as a monomer, in the presence or absence of a peroxide.

[0216] In a preferred embodiment, the elastomer is an anhydride modified elastomer.

[0217] Among these, modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof onto a polyolefin, an aromatic compound-conjugated diene copolymer, or a hydrogenated aromatic compound-conjugated diene copolymer in the presence or absence of a peroxide are more preferred, and among these, modified products obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof onto an ethylene-α-olefin copolymer, or a hydrogenated aromatic compound-conjugated diene block copolymer in the presence or absence of a peroxide are particularly preferred.

[0218] Specific examples of the α,β-unsaturated dicarboxylic acid and its derivatives include maleic acid, fumaric acid, maleic anhydride, and fumaric anhydride, with maleic anhydride being particularly preferred.

[0219] In one embodiment, the elastomer may be a mixture of an elastomer having an acidic functional group and an elastomer not having an acidic functional group. When the total of the elastomer having an acidic functional group and the elastomer not having an acidic functional group is 100% by mass, the mixing ratio of the elastomer having an acidic functional group is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and most preferably 40% by mass or more, from the viewpoint of maintaining high toughness and physical property stability of the resin composition. There is no particular upper limit, and substantially all of the elastomer may be an elastomer having an acidic functional group, but from the viewpoint of not causing problems in flowability, it is desirable to have 80% by mass or less.

[0220] When the second component contains or is a polymer, the polymer may form a particulate dispersed phase (dispersed particles) in the resin composition. In this case, the dispersed particle size is preferably 3 μm or less, more preferably 2 μm or less, and most preferably 1 μm or less, as a number average particle size. The lower limit is not particularly limited, but is, for example, 0.01 μm. From the viewpoint of high toughness and physical property stability, it is preferable to set it within the above-mentioned range.

[0221] In the resin composition, the amount of the polymer as the second component relative to 100% by mass of the entire resin composition is preferably 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, and preferably 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. When the amount of the polymer is within the above range, it is preferable from the viewpoint of high tensile elongation, high flexural modulus, low thermal expansion coefficient, and / or good physical property stability.

[0222] Additional Ingredients The resin compositions according to the aspects A to C may further contain additional components as necessary to improve their performance. Examples of the additional components include dispersants, fillers other than organic fibers, compatibilizers, plasticizers, polysaccharides such as starches and alginic acid, natural proteins such as gelatin, glue, and casein, inorganic compounds such as zeolites, ceramics, talc, silica, metal oxides, and metal powders, colorants, fragrances, pigments, flow regulators, leveling agents, conductive agents, antioxidants, antistatic agents, ultraviolet absorbers, ultraviolet dispersants, and deodorants. The content ratio of any additional component in the resin composition is appropriately selected within a range that does not impair the desired effects of the present invention, and may be, for example, 0.01 to 50% by mass, or 0.1 to 30% by mass.

[0223] The dispersant is preferably a compound capable of reacting or interacting with the second component. For example, when the second component has a hydrogen bond-forming structure (e.g., a hydroxyl group, etc.), the dispersant is preferably a compound capable of reacting or hydrogen bonding with the hydrogen bond-forming structure. Suitable examples of the dispersant are one or more selected from the group consisting of cellulose derivatives, polyalkylene oxides, amides, and amines. Among them, when the second component contains cellulose, cellulose derivatives are preferred because they are cellulose-based substances and therefore have high affinity with the cellulose, while they are also thermoplastic resins, and therefore have a high effect of improving the dispersion stability of cellulose in the resin composition. The dispersant is preferably one having a boiling point higher than that of water. Note that a boiling point higher than that of water refers to a boiling point higher than the boiling point at each pressure in the vapor pressure curve of water (for example, 100°C under 1 atmosphere).

[0224] In the resin composition, the amount of dispersant per 100 parts by mass of the second component is preferably 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more, or 20 parts by mass or more from the viewpoints of good dispersion of the second component and, when the second component contains organic fibers, network formation between the fibers, and is preferably 500 parts by mass or less, or 300 parts by mass or less, or 200 parts by mass or less from the viewpoint of reducing variation in the performance of the resin composition.

[0225] <Characteristics of resin composition> The resin compositions obtained by the methods according to the aspects A to C may have the following properties.

[0226] <Average fiber diameter and L / D of organic fibers in resin composition> In one embodiment, the average fiber diameter of the organic fibers in the resin composition may be 1000 nm or less, or 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less, or 200 nm or less, or 150 nm or less, or 100 nm or less, and may be 2 nm or more, or 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, or 30 nm or more, or 40 nm or more, or 50 nm or more, or 100 nm or more.

[0227] The average fiber length / average fiber diameter ratio (L / D) of the organic fibers in the resin composition may be, in one embodiment, 30 or more, or 50 or more, or 80 or more, or 100 or more, and in one embodiment, 5,000 or less, or 4,000 or less, or 3,000 or less.

[0228] <Thixotropy index> In the resin composition obtained by the method according to the aspects A to C, the second component can be uniformly dispersed. The thixotropy index of the resin composition is an index of the dispersion uniformity of the second component, and the higher the dispersion uniformity, the higher the thixotropy index. This phenomenon can be remarkable when the second component contains organic fibers, particularly cellulose fibers. The thixotropy index of the resin composition is preferably 2 or more, or 3 or more, or 4 or more in terms of good dispersion uniformity of the second component, and is preferably 10 or less, or 9 or less, or 8 or less in terms of ease of production of the resin composition. The thixotropy index is measured by using a dynamic viscoelasticity measuring device at a melting point of the thermoplastic resin contained in the resin composition (the melting point of the highest temperature when multiple thermoplastic resins are used) +25°C, at a shear rate of 10 seconds. -1 Viscosity vs. shear rate at 1 s -1 This is the value calculated as the ratio of the viscosity at

[0229] <Tensile elongation> In one embodiment, the tensile elongation of the resin composition measured in accordance with ISO 527-1 may be 2% or more, or 3% or more, or 5% or more, and from the viewpoint of ease of manufacture of the resin composition, may be 500% or less, or 300% or less, or 100% or less.

[0230] <Flexural modulus> In one embodiment, the flexural modulus of the resin composition measured in accordance with ISO 178 may be 1 GPa or more, or 2 GPa or more, or 3 GPa or more, and from the viewpoint of ease of production of the resin composition, may be 20 GPa or less, or 15 GPa or less, or 10 GPa or less.

[0231] <Tensile strength> In one embodiment, the tensile strength of the resin composition measured in accordance with ISO 527-1 may be 10 MPa or more, or 20 MPa or more, or 50 MPa or more, and from the viewpoint of ease of manufacture of the resin composition, may be 300 MPa or less, or 250 MPa or less, or 150 MPa or less.

[0232] <Coefficient of linear thermal expansion> In one embodiment, the linear thermal expansion coefficient of the resin composition measured by thermomechanical analysis (TMA) in accordance with ISO11359-2 may be 140 ppm / K or less, or 100 ppm / K or less, or 70 ppm / K or less, or 60 ppm / K or less, or 50 ppm / K or less, or 45 ppm / K or less, or 40 ppm / K or less, or 35 ppm / K or less in a temperature range of 20°C to 100°C, and from the viewpoint of ease of production of the resin composition, may be 5 ppm / K or more, or 10 ppm / K or more.

[0233] <Applications of resin composition> The resin compositions according to embodiments A to C are useful as substitutes for steel plates, fiber-reinforced plastics (e.g., carbon fiber-reinforced plastics, glass fiber-reinforced plastics, etc.), resin composites containing inorganic fillers, etc. Suitable applications of the resin compositions include industrial machine parts, general machine parts, automobile, railway, vehicle, ship, and aerospace-related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, housing parts for wind power generation, containers and packaging parts, etc. EXAMPLES

[0234] The following examples further illustrate exemplary aspects of the present invention, but the present invention is not limited to these examples.

[0235] (1) Example A (Example Related to Aspect A of the Present Disclosure) Evaluation method <Gap between the cylinder inner wall and the screw> It was obtained by direct measurement using a caliper. Specifically, the gap between the cylinder inner wall and the screw at the widest part of the flow path of the mixture was measured. For the sealing, the gap between the sealing outer edge and the cylinder inner wall was measured, and for the kneading disk and flight, the gap between the minor axis direction outer edges of these and the cylinder inner wall was measured.

[0236] <Tensile elongation and flexural modulus of mixture and resin composition> From the obtained mixture or resin composition, a multipurpose test piece conforming to ISO294-3 was molded using an injection molding machine under conditions conforming to JIS K6920-2. The multipurpose test piece was measured for tensile elongation at break conforming to ISO527 and flexural modulus conforming to ISO178. Since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.

[0237] <Charpy impact strength of resin composition> The Charpy impact strength was measured by the method described in ISO179-1 using the multipurpose test piece prepared in the same manner as above.

[0238] <Average fiber length, average fiber diameter and L / D of organic fibers used and organic fibers in resin composition> The wet cake was diluted to 0.01% by mass with tert-butanol, dispersed using a high-shear homogenizer (manufactured by IKA, product name "Ultra Turrax T18") at a processing condition of 25,000 rpm for 5 minutes, cast onto mica, air-dried, and measured with a high-resolution scanning microscope. The measurement was performed by adjusting the magnification so that at least 100 organic fibers were observed, and the length (L), major axis (D) and ratio of these of 100 randomly selected organic fibers were obtained, and the arithmetic average of the 100 organic fibers was calculated.

[0239] Regarding the organic fibers in the resin composition, the resin components were dissolved in hexafluoroisopropanol when the polymer was polyamide, or in xylene when the polymer was polypropylene, to separate the organic fibers, which were then thoroughly washed with the above-mentioned solvent and replaced with tert-butanol to obtain a wet cake.

[0240] <Average particle size of dried organic fiber used> The d50 particle size was measured using a powder tester, model PT-X, manufactured by Hosokawa Micron Corporation.

[0241] <Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio of cellulose fiber and chitosan fiber> [Preparation of porous sheet] First, the wet cake was added to tert-butanol, and further dispersed in a mixer or the like until no aggregates were formed. The concentration was adjusted to 0.5% by mass per 0.5 g of organic fiber solids. 100 g of the resulting tert-butanol dispersion was filtered on filter paper, dried at 150°C, and the filter paper was peeled off to obtain a sheet. The air resistance of this sheet was 10 g / m2. 2 The porous sheets with a permeability of 100 sec / 100 ml or less were used as measurement samples. The basis weight W (g / m2) of the sample left standing for one day in an environment of 23°C and 50% RH2 After measuring the air permeability, the air permeability resistance R (sec / 100ml) was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model EG01). 2 The value per unit area was calculated. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10

[0242] [measurement] 0.88 g of the porous sheet was weighed, cut into small pieces with scissors, lightly stirred, 20 mL of pure water was added, and left for one day. Next, the water and solids were separated by centrifugation. Next, 20 mL of acetone was added, lightly stirred, and left for one day. Next, the acetone and solids were separated by centrifugation. Next, 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated again by centrifugation, and then 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated by centrifugation, and 19.2 g of N,N-dimethylacetamide solution prepared so that lithium chloride was 8 mass percent was added to the solids, and it was stirred with a stirrer and confirmed to be dissolved by visual inspection. The solution in which the organic fibers were dissolved was filtered through a 0.45 μm filter, and the filtrate was used as a sample for gel permeation chromatography. The apparatus and measurement conditions used are as follows. Equipment: Tosoh HLC-8120 Column: TSKgel SuperAWM-H (6.0mm I.D. x 15cm) x 2 Detector: RI detector Eluent: N,N-dimethylacetamide (lithium chloride 0.2%) Flow rate: 0.6mL / min Calibration curve: Pullulan conversion

[0243] <Crystallization of cellulose fibers> The porous sheet was subjected to X-ray diffraction measurement, and the crystallinity was calculated according to the following formula. Crystallinity (%)=[I (200) -I(amorphous) ] / I (200) ×100 I (200) : Diffraction peak intensity due to 200 plane (2θ=22.5°) in cellulose I crystal I (amorphous) : The halo peak intensity due to the amorphous phase in cellulose I crystals, which is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200 plane (2θ=18.0°) (X-ray diffraction measurement conditions) Equipment: MiniFlex (Rigaku Corporation) Operation axis 2θ / θ Source CuKα Measurement method: Continuous Voltage 40kV Current 15mA Starting angle 2θ=5° End angle 2θ=30° Sampling width 0.020° Scan speed: 2.0° / min Sample: A porous sheet is attached onto the sample holder.

[0244] <Average content of alkali-soluble polysaccharides in cellulose fibers> The alkali-soluble polysaccharide content was calculated by subtracting the α-cellulose content from the holocellulose content (Wise method) according to the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pp. 92-97, 2000) for cellulose. The alkali-soluble polysaccharide content was calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents was taken as the average alkali-soluble polysaccharide content of cellulose.

[0245] <Degree of substitution (DS) of cellulose fiber> The infrared spectrum of the porous sheet at five points was measured by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Co., Ltd.) The infrared spectrum measurement was performed under the following conditions. Accumulation count: 64 times, Wavenumber resolution: 4cm -1 , Measurement wave number range: 4000~600cm -1 , ATR crystal: Diamond, Incident angle: 45° From the obtained IR spectrum, the IR index was calculated according to the following formula (1): IR index = H1730 / H1030 (1) In the formula, H1730 and H1030 are at 1730 cm -1 , 1030cm -1 (absorption band of CO stretching vibration of cellulose backbone chain) -1 and 1500cm -1 The line connecting the -1 and 1500cm -1 The line connecting these points is taken as the baseline, and the absorbance is calculated when this baseline is taken as 0. Then, the average degree of substitution at each measurement location was calculated from the IR index according to the following formula (2), and the average value was taken as DS. DS = 4.13 × IR index (2)

[0246] <Content of particles with a diameter of 50 μm or more in the mixture and resin composition> A multipurpose test piece conforming to ISO294-3 was molded from the mixture or resin composition using an injection molding machine under conditions conforming to JIS K6920-2. A sample of approximately 2 mm square was cut out from this test piece, and the aggregates were analyzed using an X-CT (X-ray CT device) (Skyscan1272, manufactured by Bruker Japan). The measurement conditions are as follows. Tube voltage: 40kV Tube current: 100μA Pixel resolution: 1.2μm Detector pixel count: 2452 x 1640 pixels Number of times: 4 Measurement angle step: 0.2 degrees Scan range: 0~180 degrees In addition, the measured data was smoothed using a Kuwahara filter across two pixels in the 3D direction to improve image quality.

[0247] The 3D data thus obtained was automatically binarized using the triangle method, and pixels containing only aggregates were extracted. The aggregates had a sphere-equivalent volume of (4 / 3)×π×25 3 μm 3 The content (volume %) of particles with a diameter of 50 μm or more in the mixture or resin composition was calculated from the ratio of the sum of the pixels of the aggregates that were equal to or larger to the sum of the pixels in the entire observation area, and the value obtained by dividing this content (volume %) of particles with a diameter of 50 μm or more by the total content (volume %) of organic fibers calculated from the amount of organic fibers in the mixture or resin composition was considered to be the content (mass %) of particles with a diameter of 50 μm or more in the organic fibers.

[0248] <Particle size of dispersed phase in resin composition> The cross section of the resin composition was observed using a scanning electron microscope to measure the particle size of the dispersed phase. The styrene-based thermoplastic elastomer was dyed by impregnating it with an aqueous solution of ruthenium tetroxide. The polyamide resin was dyed by impregnating it with an aqueous solution of phosphotungstic acid.

[0249] ≪Materials used≫ <First ingredient> Polyamide 6 (PA6): (Ube Industries: 1013B) Polypropylene (PP): (Prime Polymer: J105G) Polyacetal (POM): (Asahi Kasei: HC450)

[0250] <Second ingredient> [Acid-modified polyphenylene ether (m-PPE)] Asahi Kasei: R4919 [Styrene-ethylene-butadiene-styrene copolymer (SEBS)] Asahi Kasei: Tuftec H1052

[0251] [CNF-A] Commercially available Celish KY100G (manufactured by Daicel Finechem) was used as the CNF-A cake.

[0252] [CNF-B] (Acetylated CNF) One part by mass of cotton linter pulp was stirred in 30 parts by mass of dimethyl sulfoxide (DMSO) at room temperature for 1 hour at 500 rpm using a single-shaft stirrer (DKV-1 φ125 mm dissolver manufactured by IMEX).The mixture was then fed to a bead mill (NVM-1.5 manufactured by IMEX) using a hose pump and circulated for 180 minutes using only DMSO to obtain a slurry S1 (DMSO solvent) with a solid content of 3.2% by mass as a fine cellulose fiber slurry.

[0253] During circulation operation, the rotation speed of the bead mill was 2500 rpm, the peripheral speed was 12 m / s, the beads used were made of zirconia, had a diameter of 2.0 mm, and a filling rate of 70% (the slit gap of the bead mill was 0.6 mm). During circulation operation, the slurry temperature was controlled at 40°C using a chiller to absorb heat generated by friction.

[0254] The slurry S1 was charged into an explosion-proof disperser tank, and then 3.2 parts by mass of vinyl acetate and 0.49 parts by mass of sodium bicarbonate were added. The temperature inside the tank was raised to 50°C and the mixture was stirred for 120 minutes to obtain a slurry (DMSO solvent) with a solid content of 2.9% by mass.

[0255] To stop the reaction, 30 parts by mass of pure water was added and thoroughly stirred, then the mixture was placed in a dehydrator and concentrated. The obtained wet cake was dispersed again in 30 parts by mass of pure water, stirred, and concentrated. This washing procedure was repeated a total of five times to remove unreacted reagents and solvent, and 10 parts by mass of acetylated fine cellulose fiber cake (CNF-B cake) (water solvent) with a solid content of 10% by mass was obtained. A porous sheet was made from this cake and the degree of acyl substitution (DS) was determined, which was DS = 1.0.

[0256] [CNF-C] (CNF processed with a disc refiner) 3 parts by mass of cotton linter pulp was immersed in 27 parts by mass of water and heat-treated in an autoclave at 130°C for 4 hours. The resulting swollen pulp was washed with water to obtain purified pulp (30 parts by mass) containing water. Next, 170 parts by mass of water was added to 30 parts by mass of purified pulp containing water to disperse it in water (solid content rate 1.5% by mass), and the aqueous dispersion was beaten for 20 minutes using a SDR14 lab refiner (pressure type DISK type) manufactured by Aikawa Iron Works Co., Ltd. as a disc refiner device with a clearance between discs of 1 mm. Then, the mixture was concentrated to a solid content rate of 10% by mass using a dehydrator to obtain a CNF-C cake (water solvent).

[0257] [CNF-D] (CNF-C further defibrated using a high-pressure homogenizer) The CNF-C cake was thoroughly beaten under conditions that reduced the clearance to a level close to zero, to obtain a beaten water dispersion (solid content: 1.5% by mass). The obtained beaten water dispersion was then subjected to a high-pressure homogenizer (NSO15H, manufactured by Niro Soavi, Italy) for 15 cycles at an operating pressure of 100 MPa to obtain a cellulose fiber slurry (solid content: 1.5% by mass). The mixture was then concentrated to a solid content of 10% by mass using a dehydrator to obtain a CNF-D cake (water solvent).

[0258] [CNF-E] (Acetylated CNF) It was produced in the same manner as CNF-B, except that the reaction time was 60 minutes. A porous sheet was made from this cake, and the degree of acyl substitution (DS) was determined, which was DS = 0.5.

[0259] [Cellulose nanocrystals] Ceolus FD-301 (manufactured by Asahi Kasei Corporation) was used.

[0260] [Chitosan fiber] Binfis Efo-08002 (manufactured by Sugino Machine) was used.

[0261] [Aramid fiber] A Tiara KY400S (manufactured by Daicel FineChem) was used.

[0262] The properties of the organic fibers are shown in Table 1.

[0263] <Dispersant> Polyethylene oxide-polypropylene oxide copolymer (PEG-PPG) (Sanyo Chemical: GL-3000)

[0264] <Mixing method> <Extruder screw configuration> As shown in Table 2, screws 1 to 6 were designed with high load zone 1, high load zone 2, high load zone 3, and a distributive mixing zone. In the first half of the high load zone, a kneading element consisting of a diverting flight screw, a notched screw, a kneading disk, an eccentric multi-row disk, or an eccentric multi-row screw was arranged, and a seal ring with a predetermined gap was arranged downstream to block the mixture. In the distributive mixing zone, two neutral kneading disks and one counterclockwise screw were arranged in the cylinder 11 in this order.

[0265] <Mixing operation> [Example A1] A resin composition was produced by preparing a dried cellulose fiber material and mixing the dried cellulose fiber material with a resin according to the following procedure.

[0266] (Production of dried cellulose fibers) A dispersant was added to a cellulose fiber cake (10% solids by mass) in an amount of 43 parts by mass per 100 parts by mass of cellulose solids, and the mixture was thoroughly stirred to obtain a cellulose fiber cake containing a dispersant. These were placed in a drying device as raw materials and dried at a specified shear rate, reduced pressure, and heating temperature (jacket temperature or hot air temperature). The moisture content was measured using an infrared heating moisture meter (MX-50 (A&D)), and the time when the moisture content reached 7% by mass or less (93% by mass or more of solids) was defined as the end point of drying. The conditions were as follows:

[0267] Planetary Mixer (PM) Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type) Conditions: Jacket temperature 60°C, stirring at 307 rpm, pressure reduced to -90 kPa with a vacuum pump. Drying under reduced pressure was carried out until the product temperature reached 50°C. The clearance was measured as the minimum distance between the hook wing (diameter 100 mm) and the jacket. The drying time under these conditions was 180 minutes. The drying temperature was calculated by measuring the surface temperature of the jacket at three points and averaging the results.

[0268] (dispersion mixing) Polyamide 6 was fed into the extruder at 2 kg / h and dried cellulose fiber was fed at 2.86 kg / h (2 kg / h as cellulose), and the mixture was heated, melted, and kneaded in the dispersion mixing zone to obtain a dispersion mixture.

[0269] (distribution mixing) Polyamide 6 was added to the dispersion mixture at 4.86 kg / h at 15.14 kg / h by side feed, and then the mixture was heated, melted, and kneaded in a distributive mixing zone to obtain a resin composition. The resin composition obtained was processed into pellets using a pelletizer. In terms of extrusion characteristics, if the screen mesh was clogged within one hour of starting the extruder operation during extrusion processing, the operating stability was evaluated as "poor," and if it was not clogged, the operating stability was evaluated as "good."

[0270] [Examples A2 to A19, Comparative Examples A1 to A3] Resin compositions were produced and various evaluations were carried out in the same manner as in Example A1, except that the components of the resin compositions and the settings of the extruder were changed as shown in Tables 3 to 5. The results are shown in Tables 3 to 5.

[0271] [Table 1]

[0272] [Table 2]

[0273] [Table 3]

[0274] [Table 4]

[0275] [Table 5]

[0276] (2) Example B (Example relating to aspect B of the present disclosure) Evaluation method <Gap between the cylinder inner wall and the screw> Measurements were carried out in the same manner as in Example A.

[0277] <Mixture filling rate> During extrusion, the screw rotation and the raw material supply were suddenly stopped, the screw was pulled out, and the mixture adhering to the screw surface was sampled and weighed, and the volume of the filled mixture was calculated by dividing the volume by the density of the mixture. The mixture packing rate was then calculated by dividing the volume of the filled mixture by the void volume described below.

[0278] <Space volume ratio> The void volume was calculated by subtracting the screw volume (the sum of the element volume and the shaft volume) from the cylinder volume of the extruder, and the void volume was divided by the cylinder volume to calculate the void volume ratio.

[0279] <Zone Length> The total length of the screw parts constituting the dispersive mixing zone and the distributive mixing zone was defined as the zone length.

[0280] <Tensile elongation and flexural modulus of mixture and resin composition> From the obtained mixture or resin composition, a multipurpose test piece conforming to ISO294-3 was molded using an injection molding machine under conditions conforming to JIS K6920-2. The multipurpose test piece was measured for tensile elongation at break conforming to ISO527-1 and flexural modulus conforming to ISO178. Since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.

[0281] <Content of particles with a diameter of 50 μm or more in the mixture and resin composition> Measurements were carried out in the same manner as in Example A.

[0282] <Average fiber diameter and L / D of organic fibers used and organic fibers in resin composition> Measurements were carried out in the same manner as in Example A.

[0283] <Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio of cellulose fiber and chitosan fiber> Measurements were carried out in the same manner as in Example A.

[0284] <Crystallization of cellulose fibers> A porous sheet was prepared and measured in the same manner as in Example A.

[0285] <Average content of alkali-soluble polysaccharides in cellulose fibers> Measurements were carried out in the same manner as in Example A.

[0286] <Degree of substitution (DS) of cellulose fiber> Measurements were carried out in the same manner as in Example A.

[0287] ≪Materials used≫ The same as in Example A was used.

[0288] <Mixing method> [Extruder configuration] Mixing was carried out using a twin-screw extruder (STEER OMEGA30H, L / D=72) with 15 cylinder blocks. A vent port was installed at the top of cylinder 14 to enable reduced pressure suction, and vacuum suction was performed. A 50-mesh screen mesh was installed between the die adapter and the die head.

[0289] <Extruder screw configuration> As shown in Table 6, screws 1 to 5 were designed with a first dispersive mixing zone, a second dispersive mixing zone, and a distributive mixing zone. The first dispersive mixing zone and the second dispersive mixing zone each have a kneading element consisting of a diverting flight screw, a notched screw, a kneading disk, an eccentric multi-row disk, or an eccentric multi-row screw in the first half, and a seal ring and / or a counterclockwise screw in the second half to retain the mixture. The distributive mixing zone has two neutral kneading disks in the cylinder 11, followed by one counterclockwise screw.

[0290] <Mixing operation> [Example B1] A resin composition was produced by preparing a dried cellulose fiber material and mixing the dried cellulose fiber material with a resin according to the following procedure.

[0291] (Production of dried cellulose fibers) A dispersant was added to the cellulose fiber cake (10% solid content by mass) in an amount of 43 parts by mass per 100 parts by mass of cellulose solid content, and the mixture was thoroughly stirred to obtain a cellulose fiber cake containing the dispersant. These were put into a drying device as raw materials and dried at a specified shear rate, reduced pressure, and heating temperature (jacket temperature or hot air temperature). The moisture content was measured using an infrared heating moisture meter (MX-50 (manufactured by A&D)), and the time when the moisture content became 7% by mass or less (93% by mass or more of solid content) was defined as the end point of drying. The conditions were as follows. After the dried cellulose fiber body was supported on agar, X-CT analysis was performed using the method described above, and it was found that the cellulose nanofibers contained more than 50% by mass of particles with a diameter of 50 μm or more, which were aggregates of cellulose nanofibers.

[0292] Planetary Mixer (PM) Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type) Conditions: Jacket temperature 60°C, stirring at 307 rpm, pressure reduced to -90 kPa with a vacuum pump. Drying under reduced pressure was carried out until the product temperature reached 50°C. The clearance was measured as the minimum distance between the hook wing (diameter 100 mm) and the jacket. The drying time under these conditions was 180 minutes. The drying temperature was calculated by measuring the surface temperature of the jacket at three points and averaging the results.

[0293] (dispersion mixing) The extruder was charged with 2 kg / h of polyamide 6 and 2.86 kg / h of dried cellulose fiber (2 kg / h as cellulose), and the mixture was heated and melted in the first dispersing and mixing zone to obtain a first dispersed mixture. The mixture was then heated and melted in the second dispersing and mixing zone to obtain a second dispersed mixture.

[0294] (distribution mixing) Polyamide 6 was added to the second dispersion mixture at 4.86 kg / h by side feed at 15.14 kg / h, and then the mixture was heated, melted, and kneaded in a distributive mixing zone to obtain a resin composition. The resin composition obtained was processed into pellets using a pelletizer. In terms of extrusion characteristics, if the screen mesh was clogged within one hour of starting the extruder operation during extrusion processing, the operating stability was evaluated as "poor," and if it was not clogged, the operating stability was evaluated as "good."

[0295] [Examples B2 to B7, Comparative Example B1] Resin compositions were produced in the same manner as in Example B1, except that the components of the resin compositions and the settings of the extruder were changed as shown in Table 7, and various evaluations were carried out. The results are shown in Table 7.

[0296] [Table 6]

[0297] [Table 7]

[0298] (3) Example C (Example relating to aspect C of the present disclosure) Evaluation method <Gap between the cylinder inner wall and the screw> Measurements were carried out in the same manner as in Example A.

[0299] <Mixture filling rate> During extrusion, the screw rotation and the raw material supply were suddenly stopped, the screw was pulled out, and the mixture adhering to the screw surface was sampled and weighed, and the volume of the filled mixture was calculated by dividing the volume by the density of the mixture. The mixture packing rate was then calculated by dividing the volume of the filled mixture by the void volume described below.

[0300] <Zone length of the area where the mixture pressure is 0.3 MPa or more / cylinder inner diameter ratio> The resin pressure in each zone was measured by installing multiple resin pressure gauges in the cylinder of the extruder and monitoring the resin pressure during extrusion. The resin pressure was calculated by dividing the total length of the zone where the mixed pressure was 0.3 MPa or more by the inner diameter of the cylinder.

[0301] <Space volume ratio> The void volume was calculated by subtracting the screw volume (the sum of the element volume and the shaft volume) from the barrel volume of the extruder, and the void volume was divided by the barrel volume to calculate the void volume ratio.

[0302] <Zone Length> The total length of the screw parts constituting the dispersive mixing zone and the distributive mixing zone was defined as the zone length.

[0303] <Tensile elongation and flexural modulus of mixture and resin composition> From the obtained mixture or resin composition, a multipurpose test piece conforming to ISO294-3 was molded using an injection molding machine under conditions conforming to JIS K6920-2. The multipurpose test piece was measured for tensile elongation at break conforming to ISO527-1 and flexural modulus conforming to ISO178. Since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.

[0304] <Thixotropy index> The viscoelasticity of the above multipurpose test specimen in a molten state was measured under the following test conditions. Device name: ARES G2 TA Instruments Japan Co., Ltd. Measurement temperature: 250°C (melting point of polyamide + 25°C), 185°C (melting point of polypropylene + 25°C) Shear rate: 1.0 to 40 s -1 A 25mm / 40mm parallel plate was used with a gap of 1mm. From the measurement results, the thixotropy index was calculated according to the following formula. Thixotropy index = (shear rate 1s -1 Viscosity at shear rate 10s -1 (viscosity at

[0305] <Improvement rate of physical properties per unit mass of cellulose fiber in the mixture (improvement rate of bending modulus)> The cellulose fiber concentration in the mixture was determined from the ratio of the amount of cellulose fiber fed to the extruder during extrusion, and the improvement rate of physical properties per unit mass of cellulose fiber in the mixture was calculated according to the following formula. (Flexural modulus of mixture - Flexural modulus of base resin) / Cellulose fiber concentration (mass%)

[0306] <Charpy impact strength> Measurements were carried out in the same manner as in Example A.

[0307] <Average fiber length, average fiber diameter and L / D of cellulose fibers used and cellulose fibers in resin composition> Measurements were carried out in the same manner as in Example A.

[0308] <Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio of cellulose fibers> Measurements were carried out in the same manner as in Example A.

[0309] <Crystallization of cellulose fibers> A porous sheet was prepared and measured in the same manner as in Example A.

[0310] <Average content of alkali-soluble polysaccharides in cellulose fibers> Measurements were carried out in the same manner as in Example A.

[0311] <Content of particles with a diameter of 50 μm or more in the resin composition> Measurements were carried out in the same manner as in Example A.

[0312] <Particle size of dispersed phase in resin composition> Measurements were carried out in the same manner as in Example A.

[0313] ≪Materials used≫ The polymer, organic fiber and dispersant used were the same as those used in Example A.

[0314] <Mixing method> <Extruder screw configuration> As shown in Table 8, screws 1 to 5 were designed with zones 1 and 2. Zone 1 of screw 1 was a dispersive mixing zone, and was designed to have multiple kneading zones that combined kneading elements consisting of a divergent flight screw, a notched screw, a kneading disk, an eccentric multi-row disk, and an eccentric multi-row screw with a retention element consisting of a seal ring and / or a counterclockwise screw. Zone 2 of screws 1 to 5 was a distributive mixing zone, and two neutral kneading disks were arranged in cylinder 11, followed by one counterclockwise screw. Zone 1 of screw 2 was a distributive mixing zone and was designed with a combination of single and / or multiple kneading disks, single and / or multiple counterclockwise screws. Zone 1 of screw 3 is a dispersive mixing zone, and is designed to have one more kneading zone than screw 1. The zone length / cylinder inner diameter ratio and void volume fraction of each screw configuration are shown in Table 8.

[0315] <Mixing operation> [Example C1] A resin composition was produced by preparing a dried cellulose fiber material and mixing the dried cellulose fiber material with a polymer according to the following procedure.

[0316] (Production of dried cellulose fibers) A dispersant was added to a cellulose fiber cake (10% solids by mass) in an amount of 43 parts by mass per 100 parts by mass of cellulose solids, and the mixture was thoroughly stirred to obtain a cellulose fiber cake containing a dispersant. These were placed in a drying device as raw materials and dried at a specified shear rate, reduced pressure, and heating temperature (jacket temperature or hot air temperature). The moisture content was measured using an infrared heating moisture meter (MX-50 (A&D)), and the time when the moisture content reached 7% by mass or less (93% by mass or more of solids) was defined as the end point of drying. The conditions were as follows:

[0317] Planetary Mixer (PM) Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type) Conditions: Jacket temperature 60°C, stirring at 307 rpm, pressure reduced to -90 kPa with a vacuum pump. Drying under reduced pressure was carried out until the product temperature reached 50°C. The clearance was measured as the minimum distance between the hook wing (diameter 100 mm) and the jacket. The drying time under these conditions was 180 minutes. The drying temperature was calculated by measuring the surface temperature of the jacket at three points and averaging the results.

[0318] (dispersion mixing) Polyamide 6 was fed into the extruder at 2 kg / h and dried cellulose fiber was fed at 2.86 kg / h (2 kg / h as cellulose), and the mixture was heated, melted, and kneaded in the dispersion mixing zone to obtain a dispersion mixture.

[0319] (distribution mixing) Polyamide 6 was added to the dispersion mixture at 4.86 kg / h at 15.14 kg / h by side feed, and then the mixture was heated, melted, and kneaded in a distributive mixing zone to obtain a resin composition. The resin composition obtained was processed into pellets using a pelletizer. In terms of extrusion characteristics, if the screen mesh was clogged within one hour of starting the extruder operation during extrusion processing, the operating stability was evaluated as "poor," and if it was not clogged, the operating stability was evaluated as "good."

[0320] [Examples C2 to C9, Comparative Example C1] Resin compositions were produced and various evaluations were carried out in the same manner as in Example C1, except that the formulation of the resin composition and the setting conditions of the extruder were changed as shown in Tables 9 and 10. The results are shown in Tables 9 and 10.

[0321] [Table 8]

[0322] [Table 9]

[0323] [Table 10] [Industrial Applicability]

[0324] The resin composition obtained by the resin composition production method disclosed herein can be suitably applied to a wide range of applications, such as industrial machine parts, general machine parts, automobile, railway, vehicle, ship, and aerospace related parts, electronic and electrical parts, building and civil engineering materials, daily necessities, sports and leisure goods, housing parts for wind power generation, containers and packaging parts, etc. [Explanation of symbols]

[0325] 100,200,300,400,600,800 Extruder 101, 201, 301 Mixing zone 102,202,302 Melt Zone N1, N2, N3 Narrow gap zone D1 Pressure Drop Zone H1, H2, H3 high pressure zone 11, 12, 13, 14, 21, 22, 31, 32, 33, 34 Other Zones 401,601,801 Dispersed Mixed Zone 402,602,802 Distribution Mixing Zone 403,404,603,604,803,804 Melt Zone 41 First Dispersive Mixing Zone 42 Second Dispersive Mixing Zone 41a Inlet to the first dispersive mixing zone 41b Outlet from the first dispersive mixing zone 42a Inlet to the second dispersive mixing zone 42b Outlet from the second dispersive mixing zone a1 1st component a2 second component b Resin composition L Cylinder length direction

Claims

1. A method for producing a resin composition including a first component and a second component, comprising: the first component is a polymer; the second component is an organic fiber or a combination of an organic fiber and a polymer different from the first component; The method includes a step of mixing a first component and a second component using an extruder having a mixing zone including a pressure drop zone; The pressure drop zone is a region where the pressure of the influent into the pressure drop zone is 0.5 to 20 MPa, and the ratio of the pressure of the effluent from the pressure drop zone to the pressure of the influent into the pressure drop zone is 0.2 or less. ,method.

2. 10. The method of claim 1, further comprising the step of adding said second component to a melt of said first component prior to said kneading step to obtain a premix, said premix being fed to said kneading zone.

3. The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; The dispersive mixing zone includes a first dispersive mixing zone and a second dispersive mixing zone, which are different from each other in one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume rate; an increment [E1] of the tensile elongation of the outflow from the first dispersive mixing zone relative to the tensile elongation of the inflow to the first dispersive mixing zone, and an increment [E2] of the tensile elongation of the outflow from the second dispersive mixing zone relative to the tensile elongation of the inflow to the second dispersive mixing zone satisfy the relationship [E1]>[E2]; 3. The method according to claim 1 or 2, wherein an increment [M1] in the bending modulus of the output from the first dispersive mixing zone relative to the bending modulus of the influent to the first dispersive mixing zone and an increment [M2] in the bending modulus of the output from the second dispersive mixing zone relative to the bending modulus of the influent to the second dispersive mixing zone satisfy the relationship [M1] < [M2].

4. The method includes dispersively mixing a first component and a second component in a dispersive mixing zone of an extruder; 3. The method according to claim 1 or 2, wherein in the dispersing and mixing zone, one or more selected from the group consisting of a zone length / cylinder inner diameter ratio, mixture filling rate, temperature, pressure, and void volume ratio are varied in the cylinder length direction, thereby changing a ratio [ΔE / ΔM] of a change in tensile elongation ΔE (%) per value (l / d) obtained by dividing a progression length l (mm) of the mixture in the cylinder by a cylinder inner diameter d (mm) to a change in flexural modulus ΔM (GPa) per l / d in the cylinder length direction.

5. The method further comprising: dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, The dispersive mixing zone and the distributive mixing zone are different from each other in at least one selected from the group consisting of a zone length / cylinder inner diameter ratio, a mixture packing rate, a temperature, a pressure, and a space volume ratio; an increment [EA] of the tensile elongation of the outflow from the dispersive mixing zone relative to the tensile elongation of the inflow to the dispersive mixing zone, and an increment [EB] of the tensile elongation of the outflow from the distributive mixing zone relative to the tensile elongation of the inflow to the distributive mixing zone satisfy the relationship [EA]>[EB]; 3. The method according to claim 1 or 2, wherein the increment [MA] of the bending modulus of the output from the dispersive mixing zone relative to the bending modulus of the influent to the dispersive mixing zone and the increment [MB] of the bending modulus of the output from the distributive mixing zone relative to the bending modulus of the influent to the distributive mixing zone satisfy the relationship [MA] > [MB].

6. The method further comprising: dispersively mixing the first component and the second component in a dispersive mixing zone of the extruder to obtain a dispersively mixed product; a distributive mixing step of distributively mixing at least the dispersed mixed product in a distributive mixing zone of an extruder to obtain a resin composition; Including, 3. The method according to claim 1 or 2, wherein the concentration of the second component in the dispersive mixing zone [CA] is 10% by weight to 90% by weight, the concentration of the second component in the distributive mixing zone [CB] is 1% by weight to 50% by weight, and the ratio [CA] / [CB] is 2 to 90.

7. 7. The method of claim 3, further comprising the step of adding said second component to a melt of said first component to obtain a premix prior to said dispersive mixing step, said premix being fed to said dispersive mixing zone.

8. The method according to any one of claims 1 to 7, wherein the organic fibres are cellulose fibres.

9. The method according to any one of claims 1 to 8, wherein the organic fibers in the resin composition have an average fiber diameter of 1000 nm or less and an average fiber length / average fiber diameter ratio of 30 or more.

10. The method according to any one of claims 1 to 9, wherein the organic fibres are fed to the extruder in the form of a dry mass.

11. The method according to claim 1, wherein the polymer is a crystalline thermoplastic resin having a melting point in the range of 100°C to 350°C, or an amorphous thermoplastic resin having a glass transition point in the range of 100°C to 250°C.

12. The method according to any one of claims 1 to 11, wherein the polymer is a polyolefin-based resin, a polyamide-based resin, a polyester-based resin, a polyacetal-based resin, a polyphenylene ether-based resin, a polyphenylene sulfide-based resin, or a mixture of two or more of these.

13. The method according to any one of claims 1 to 12, wherein the polymer is a thermoplastic resin and the melting point of the thermoplastic resin is 140°C or higher.